Process for the production of polyether-polysiloxane block copolymer compositions, polyether-polysiloxane block copolymer compositions and use thereof
Patent Information
- Application Number
- CN202280047442.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-04
- Filing Date
- 2022-05-31
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-05-31
AI Technical Summary
即,这些文献中的弱碱性缓冲剂,作为文字上的表现,具有多种缓冲剂、反应促进剂、催化剂改性剂、用于低臭化的添加剂等,但表达其的根本功能归结于中和或体系的pH调整,在特定量的钠盐以可溶解的少量存在于组合物中的情况下,也没有暗示本发明人等发现赋予该组合物特异性增强的表面活性能力/泡沫保持能力这样的新功能的记载
[0059]根据本发明的制造方法,可以提供一种包含(AB)n型聚醚改性有机硅组合物的得到改善的氢化硅烷化反应工艺的制造方法、以及通过该制造方法得到的组合物的整泡剂等的用途,所述(AB)n型聚醚改性有机硅组合物抑制了由原料的品质以及批次偏差引起的影响,成本低,且不易受到原料的计量误差或者批次的影响(酸值等),可以稳定且容易地制造,成本利用和供给性优异,且在聚氨酯泡沫用整泡剂的用途中具有充分的性能。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] This invention relates to an improved hydrosilylation process for manufacturing compositions containing polyether-polysiloxane block copolymers having a specific structure and a glycol ether compound. Furthermore, this invention relates to a composition containing polyether-polysiloxane block copolymers that contains a specific amount of a sodium monovalent carboxylate and exhibits improved foam reinforcement. Further, this invention relates to a surfactant containing these compositions, and a foam stabilizer for polyurethane foams (including functions as a bubble control agent and bubble stabilizer, hereinafter the same). Background Technology
[0002] Linear organopolysiloxane-polyether block copolymers, obtained by the hydrosilylation reaction of (1) organopolysiloxanes with SiH groups at both ends and (2) polyethers with C=C groups at both ends, are known as non-hydrolyzable (AB)n-type polyether-modified organosilicones (Patent Documents 1, 2). These block copolymers are obtained by hydrosilylation in toluene solvent, but toluene is usually removed from the product system by stripping under heating or reduced pressure due to its high risk of toxicity or flammability. Similarly, xylene solutions containing these block copolymers are known and commercially available, but they also have the problem of containing flammable and hazardous organic solvents.
[0003] Patent document 3 discloses an example of a solvent exchange method in which polypropylene glycol is added as a diluent after the copolymer is synthesized in toluene, and toluene is further removed by stripping. It also mentions that polyols used in polyurethane foam formulations can be used as diluents. Furthermore, as a comparative example, a commercially available foam stabilizer using long-chain alkylbenzenes as both a reaction solvent and diluent is proposed. This solvent exchange method reduces the viscosity of the (AB)n type polyether-modified silicone foam stabilizer to improve operability. It is also advantageous in terms of reducing the VOC (Volatile Organic Compound) content of the polyurethane foam, but suffers from low production efficiency due to foaming during solvent exchange. Long-chain alkylbenzenes have the advantage of simplifying the foam stabilizer manufacturing process, but they remain in the polyurethane foam, becoming a source of VOCs, and subsequently migrating (exudating) from the final product.
[0004] Patent document 4 relates to a method for manufacturing siloxane-polyoxyethylene copolymers by hydrogenation silanization under reduced pressure, disclosing an (AB)n type polyether modified silicone composition using IPP (isopropyl palmitate) as a reaction solvent and diluent. However, ester oils, represented by IPP, are prone to separation, especially at low temperatures, due to poor compatibility with the copolymer. Furthermore, when included in a foaming agent, they can contribute to VOCs and migration from polyurethane foams.
[0005] Patent document 5 discloses a technique for stably manufacturing non-hydrolyzable (AB)n type polyether-modified silicone or similar structures, particularly high molecular weight copolymers, without causing thickening or gelation. It illustrates an example where, after synthesizing the copolymer in flowing isoparaffins, unreacted low-boiling substances such as precipitates are removed by stripping (wherein a large portion of the flowing isoparaffins remains as a diluent for the copolymer). However, when included in a foaming agent, the flowing isoparaffins can become a source of VOCs and migration from the polyurethane foam.
[0006] Patent Document 6 is an invention made to solve the problems addressed in Documents 1-5, disclosing a composition, a method for manufacturing the same, a foam stabilizer comprising the same, etc., said composition containing (A) a non-hydrolyzable (AB)n-type polyether modified organosilicon, and (B) a specific glycol ether compound in which the terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and having secondary alcoholic hydroxyl groups at other ends. This (B) component can be used as a reaction solvent and diluent for manufacturing the (A) component, and further, during the formation of polyurethane foam, it is introduced into the polyurethane resin backbone through the reactivity of the hydroxyl groups, thus having the advantage of simultaneously achieving VOC minimization of the foam and efficient production of the foam stabilizer.
[0007] In Patent Document 7, in response to the problem that the hydrosilylation of compounds containing SiH compounds and compounds with olefinic unsaturated groups at the ends, based on chloroplatinic acid catalysts, cannot proceed sufficiently due to considerable side reactions in the presence of water or alcohols, a solution is proposed to implement the hydrosilylation by coexisting with a buffer aqueous solution that maintains the pH of the system at 5 to 7 even in the presence of strong acids.
[0008] Patent Document 8 discloses a method for manufacturing a side-chain polyether-modified organosilicon, characterized in that a hydrosilylation reaction of a monoalkenyl polyether with terminal hydroxyl groups is carried out solvent-free in the presence of a carboxylic acid or carboxylate represented by RCO2M (where M is selected from the group consisting of H, alkali metals, alkaline earth metals, ammonium ions, and tetraalkylphosphonium ions, and R is a monovalent hydrocarbon group with 2 to 20 carbon atoms). In the examples, 0.02 to 0.5 wt.% sodium propionate or sodium butyrate is used relative to the monoalkenyl polyether, but 85% phosphoric acid water is also mixed in the reaction system for neutralizing the polysiloxane containing SiH groups. Therefore, the actual buffer system in this system has a complex structure, and the effects of using industrially readily available buffer systems or specific amounts of buffer are neither described nor implied.
[0009] Patent Document 9 discloses a process for preparing a general side-chain polyether-modified organosilicon surfactant via a hydrosilylation reaction in a high-boiling-point polyol solvent such as dipropylene glycol that does not have olefinic unsaturated groups, and a mixture consisting of the organosilicon surfactant and the polyol solvent (here, the polyol content in the mixture is at least 5 wt.%, and it contains at least 100 ppm of an alkali metal or alkaline earth metal salt of a C2-C19 monovalent carboxylic acid as a reaction promoter). In the experimental examples in this document, an ethanolic solution of chloroplatinic acid was used as a catalyst for hydrosilylation, and sodium oleate (Example 7), sodium butyrate (Example 8), and potassium acetate (Example 9) were used as buffers at 550 ppm relative to the total mixture.
[0010] Patent Document 10 describes a surfactant composition for flexible polyurethane foam comprising 99.98–90 wt.% of a non-hydrolyzable side-chain type polyether-modified silicone suitable for the same purpose and 0.02–10 wt.% of an organic acid salt. In this technique, the addition of the organic acid salt and the manufacturing process of the polyether-modified silicone are independent of each other. The organic acid salt is added to the polyether-modified silicone in solid form or as an aqueous solution, and heating for reducing water content is arbitrary. The resulting surfactant composition improves the height and permeability of the flexible polyurethane foam. The organic acid salts tested in the examples and their addition amounts are: sodium dodecylbenzenesulfonate: 0.2–1.6 wt.%, sodium p-toluenesulfonate: 0.4 wt.%, sodium bis-(2,4,4-trimethylpentyl)phosphonate: , and potassium oleate: 0.4 wt.%.
[0011] Patent Document 11 claims a method for manufacturing a general side-chain polyether-modified organosilicon based on hydrosilylation using a platinum catalyst in an organic solvent. The method is characterized by obtaining a low-odor polyether-modified organosilicon through the use of a high-purity monoalkenyl-terminated polyether with suppressed peroxide value and total carbonyl content. The method includes a post-reaction water distillation step, the addition of a predetermined amount of antioxidant, and optionally the addition of a buffer that provides a pH of 5.5 to 8 when dissolved in water. In this technique, the buffer is added after the synthesis of the polyether-modified organosilicon. In Reference Examples 1-4, an IPA solution of chloroplatinic acid was used as the catalyst, and a methanol solution of sodium acetate (100 wt. ppm, based on sodium acetate, relative to the polyether-modified organosilicon composition excluding the organic solvent) was used as the buffer.
[0012] Patent Document 12 discloses a solvent-free continuous production process for the hydrogenation and silanization of organosilicon copolymers using a static mixing plug flow reactor. When the hydroxyl groups at the ends of the polyether are not capped, a buffer such as a carboxylate is recommended. This buffer is pre-dissolved in the polyether before being introduced into the reactor; in Example 19, sodium propionate at 100 wt.ppm relative to the polyether was used. On the other hand, in Comparative Example 12, the exact same raw materials as in Example 19 were used to produce side-chain polyether-modified organosilicon by sequentially connecting two continuous tank reactors and one plug flow reactor, with continuous supply and discharge of the raw materials.
[0013] Patent Document 13 discloses a polyorganosiloxane-polyoxyethylene block copolymer [a specific (AB)n type polyether modified organosilicon], its preparation method, and a vesicle composition containing the same. In Examples 1-4, a dimethylsiloxane solution of a 1,3-diethyl-1,1,3,3-tetramethyldisiloxane platinum complex was used as a catalyst, and the reaction was carried out in xylene solvent in the presence of sodium acetate at 484-688 ppm to prepare the (AB)n type polyether modified organosilicon. In Examples 8-11, the same (AB)n type polyether modified organosilicon was prepared by using the same catalyst and reacting in IPA solvent in the presence of sodium acetate at 438-500 ppm. These reaction solvents were removed by stripping after the reaction.
[0014] It should be noted that Patent Document 13 discloses a variety of reaction solvents that can be used as needed in the manufacture of the (AB)n type polyether modified organosilicon, including monoethers of propylene glycol or dipropylene glycol, but this is only disclosed as a non-limiting example of an optional solvent. Furthermore, among these various solvents, a large number are listed that are impractical for use in the manufacture of (AB)n type polyether modified organosilicon due to their potential to hinder the reaction, cause inhomogeneity of the reaction system, or lead to side reactions. To explore the optimal solvent, those skilled in the art would need to conduct extensive experiments to verify the reactivity and stability of these solvents, and there is a lack of specific description regarding the selection of preferred solvents. In particular, no description or suggestion is made regarding the fact that specific glycol ether compounds with (B) terminal hydrogen replaced by hydrocarbon groups having 1 to 8 carbon atoms and secondary alcoholic hydroxyl groups at other terminals can be used as a reaction solvent and diluent for the synthesis of (AB)n-type polyether-modified organosilicones with a structure suitable as the main component of a foaming agent for polyurethane foams; improvements in the industrial production process of such foaming agents based on this; and the realization or benefit of microcellularization of polyurethane foams based on the good compatibility of such foaming agents with premixed liquids. Therefore, Patent Document 13 does not provide explicit teachings that would be understandable to a person skilled in the art regarding the invention and technical benefits of Patent Document 6.
[0015] Patent document 14 discloses a manufacturing process for polyether-modified organosilicon with a -SiOC- content of less than 1 mol%. This process comprises a hydrosilylation reaction of a polyether having at least one terminal unsaturated aliphatic hydrocarbon group and an alkali metal content of less than 50 ppm with an organohydrosiloxane having an acid value of less than 0.005. In experimental examples, the synthesis reaction of general side-chain polyether-modified organosilicon was carried out entirely under solvent-free conditions. It was reported that the addition of 13 ppm sodium acetate (Comparative Example 4) or 15 ppm potassium acetate (Comparative Example 5) to the reaction system resulted in a delay in the reaction rate. This technology is based on the concept that by using refined raw materials with low ionic impurity content on both the siloxane side and the polyether side involved in the hydrosilylation, excellent reactivity is continuously maintained in the reaction system without interruption, resulting in stable and efficient production of polyether-modified organosilicon. Furthermore, various reaction solvents that can be used are disclosed, including monoethers of propylene glycol or dipropylene glycol, but no mention is made of the specific problems or causes that arise when these are used as synthetic solvents for (AB)n-type polyether-modified organosilicon. Therefore, Patent Document 14 differs from the technical concept of the present invention.
[0016] Patent Document 15 discloses compositions containing general side-chain type polyether modified organosilicon and substances similar to (B), methods for their manufacture, and foam stabilizers containing them. Paragraph 0084 shows that buffers such as alkali metal salts of carboxylic acids can be added for purposes such as suppressing side reactions, and several options regarding methods of addition. Furthermore, it describes that when a polar solvent is used in the dissolution of this salt, removal based on a stripping operation can be carried out arbitrarily before or after the main reaction begins. However, the types and methods of using buffers are limited to non-limiting disclosures, and no buffers are used in the examples / comparative examples; there is no information whatsoever regarding the preferred amount of buffer components to be added. Moreover, it is difficult to discern from Patent Document 15 the specific problems arising when using inexpensive (B) raw material as a synthesis solvent for (AB)n type polyether modified organosilicon (A), and therefore no specific and particular means are shown regarding the optimal solution.
[0017] On the other hand, Patent Documents 1-15 teach the use of a buffer containing an alkali metal salt of carboxylic acid in the process of manufacturing (AB)n type polyether modified organosilicon, etc., via a hydrosilylation reaction. However, they do not describe or imply any specific experimental examples or related technical effects of mixing a specific buffer solution into the raw material system before the reaction begins, and then removing the solvent from the buffer to start the reaction, in order to improve the hydrosilylation reaction process. In particular, these documents do not describe or imply any examples or technical effects of improving the hydrosilylation reaction process to solve quality problems in compositions containing a specific structure of "(AB)n type polyether modified organosilicon" and "a specific glycol ether compound whose terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and has secondary alcoholic hydroxyl groups at other ends" as main components.
[0018] Furthermore, in Patent Documents 1-15, the function or expected effect of the buffer is based on its function of neutralizing acidic substances in the system (thereby inhibiting side reactions during manufacturing = promoting the main reaction, or inhibiting changes over time during product storage). That is, the weakly basic buffers in these documents, as described in words, include various buffers, reaction promoters, catalyst modifiers, additives for deodorization, etc., but their fundamental function is expressed as neutralization or pH adjustment of the system. Even when a specific amount of sodium salt is present in the composition in a soluble amount, there is no indication that the inventors have discovered new functions such as giving the composition specifically enhanced surface activity / foam retention ability.
[0019] Existing technical documents
[0020] Patent documents
[0021] Patent Document 1: US Patent No. 3,957,842 (Japanese Patent Application Publication No. 56-22395)
[0022] Patent Document 2: US Patent No. 4150048
[0023] Patent Document 3: Japanese Patent Application Publication No. 08-156143
[0024] Patent Document 4: US Patent No. 5,869,727 (Japanese Patent Application Publication No. 11-116,670)
[0025] Patent Document 5: Japanese Patent Application Publication No. 2006-282820 (Japanese Patent No. 4875314)
[0026] Patent Document 6: International Publication No. 2016 / 166979 (US Patent No. 10717872)
[0027] Patent Document 7: U.S. Patent No. 3,398,174
[0028] Patent Document 8: US Patent No. 4,847,398 (Japanese Patent Publication No. 5-51619)
[0029] Patent Document 9: U.S. Patent No. 4,857,583 (Japanese Patent Application Publication No. 1-87633)
[0030] Patent Document 10: US Patent No. 5,472,987 (Japanese Patent No. 2,599,237)
[0031] Patent Document 11: US Patent No. 5,696,192 (Japanese Patent Application Publication No. 9-202829)
[0032] Patent Document 12: US Patent No. 6,593,436
[0033] Patent Document 13: International Publication No. 2005 / 103117
[0034] Patent Document 14: US Patent No. 8008407 (Japanese Patent No. 5101598)
[0035] Patent Document 15: International Publication No. 2018 / 074257 (US20200048427A1) Summary of the Invention
[0036] The problem that the invention aims to solve
[0037] As described above, (AB)n type polyether-modified silicone can be used to design the average molecular weight of the copolymer, and its surface activity or affinity for polyurethane foam systems can be controlled by the EO / PO ratio or size of the polyether portion, the weight percentage of the silicone portion, etc. Therefore, it is expected to perform excellently as a surfactant for bubble control or bubble stabilization in various polyurethane foam formulations. However, in the prior art, there are manufacturing problems, performance or quality problems directly related to the industrial production costs mentioned above, and insufficient market penetration due to these potential values.
[0038] The compositions and foam stabilizers containing (AB)n-type polyether-modified silicone and specific glycol ether compounds previously proposed by the inventors in Patent Document 6 can preferably solve the above-mentioned problems to some extent. However, when obtaining this composition, the inventors discovered a new problem: the quality of the glycol ether compound has a significant impact on the quality during manufacturing. That is, when using low-cost glycol ether compounds with high acid values, the composition sometimes becomes low in viscosity during the hydrosilylation reaction, resulting in reduced foam stability, or its transparency (transmittance) is impaired, failing to fully achieve the performance expected as a foam stabilizer.
[0039] Furthermore, the inventors discovered new problems and solutions not described in these patent documents during the present invention. In recent years, foam retention capacity has become a crucial requirement for foam stabilizers, particularly in the manufacture of microporous foams, where (AB)n-type polyether-modified silicone is the primary application. Specifically, even when designing low-density foams by reducing the amount of foam stabilizer added (cost reduction) and by increasing the amount of blowing agent or entrained gas, it is easy to obtain foams with acceptable physical properties (achieving energy savings based on lightweighting). Therefore, there is a strong demand for foam stabilizers for microporous foams with strong foam retention capacity.
[0040] The conventional method for improving foam retention is to design a foam stabilizer formulation to obtain a high molecular weight / high viscosity product with a large n-number, i.e., to react the raw material polyether with a C=C / SiH molar ratio close to 1.0. However, in this method, it is known that even small metering errors in the raw materials, batch-by-batch quality variations, or differences in manufacturing conditions can significantly affect the viscosity of the resulting foam stabilizer, leading to a high frequency of non-standard product manufacturing. Furthermore, the poor manufacturability or operability of high-viscosity products inevitably leads to further cost increases.
[0041] The technology in Patent Document 6 above provides some improvement to this complex and multifaceted problem, but there is room for further improvement in terms of industrial simplicity or production efficiency. In particular, foaming agents require inexpensive, industrially abundant, and stable supply, so there are still unresolved issues with the commercialization of foaming agent compositions obtained using existing technologies that require high levels of production management.
[0042] Given the market demand for silicone foam stabilizers for polyurethane foams and the widespread availability of high-performance silicone foam stabilizers, there is a strong desire to develop a foam stabilizer using (AB)n type polyether modified silicone, its manufacturing process, and formulations using it. This foam stabilizer should be low in cost, not easily affected by slight errors in raw materials or batch variations (acid value, etc.), stable and easy to manufacture, have excellent cost utilization and supply, and possess sufficient performance for applications as a foam stabilizer in polyurethane foams, particularly in terms of foaming properties, bubble reinforcement, bubble control, and bubble stability in the foam system.
[0043] Solution for solving the problem
[0044] In order to solve the above problems, the inventors conducted in-depth research and found that the above problems could be solved by a method for manufacturing a composition of a polyether-polysiloxane block copolymer (A') containing a specific structure having the following steps 1 to 3 (hereinafter, sometimes referred to as "this manufacturing method" or "the manufacturing method of the present invention"), thereby completing the present invention.
[0045] Step 1: will include at least
[0046] (a1) Polyethers with alkenyl groups at both ends; and
[0047] (N+S) is a sodium salt solution containing the following components (N) and (S):
[0048] (N) Sodium monovalent carboxylate salts with 2 to 18 carbon atoms.
[0049] (S) is a solvent selected from (S1) water and (S2) a monohydric saturated alcohol having 1 to 4 carbon atoms.
[0050] The process of mixing raw material components;
[0051] Process 2:
[0052] The process of removing the solvent (S) from step 1 to the outside of the system by heating and / or reducing pressure;
[0053] Step 3: A step in which the organopolysiloxanes containing SiH groups at both ends of components (a1) and (a2) undergo a hydrosilylation reaction in the presence of specific glycol ether compounds of components (N) and (B') and a hydrosilylation reaction catalyst. (Where the total amount of components (a1), (a2), and (B') is set to 100 parts by weight, the amount of component (B') used is in the range of 40 to 80 parts by weight, and relative to the amount of component (B') used, the sodium cation (Na) in component (N) is...) + The content of ) is in the range of 3.8 to 43 wt.ppm.
[0054] This manufacturing method can preferably perform steps 1 to 3 above in a single reaction vessel. Furthermore, step 1 can be a simple mixing of component (a1) and component (N+S), or it can be a mixing step containing other raw material components. In step 1, it is extremely preferable that component (a2) and the hydrosilylation reaction catalyst do not coexist in the raw material system.
[0055] This manufacturing method may further include a step selected from the following steps: a step of filtering the composition after the hydrosilylation reaction; a step of adding a polyether compound that is compatible with the above-mentioned components (A') and (B') and selected from specific components (C1) to (C3) after the hydrosilylation reaction, and mixing and homogenizing it; and a step of adding an antioxidant at any time.
[0056] Furthermore, it was found that by including (A”) a polyether-polysiloxane block copolymer with a specific structure, (B’) a specific glycol ether compound, and (N) a sodium monovalent carboxylate salt with 2 to 18 carbon atoms, the mass ratio of component (A”) to component (B’) is in the range of 20:80 to 60:40, and the sodium cation (Na) in component (N) is present in the range of 0.6 to 6.7 wt.ppm relative to the sum of components (A”) and (B’). + The present invention is made by using a foam-reinforcing composition (hereinafter, sometimes referred to as "this foam-reinforcing composition") and its use to solve the above-mentioned problems.
[0057] Furthermore, the aforementioned problems are solved by using surfactants, foam stabilizers for polyurethane foams, or premixes for polyurethane foams (hereinafter referred to as "surfactants, etc.") that include the composition obtained by the present invention. Similarly, the aforementioned problems are solved by manufacturing methods that include surfactants, etc. of the present manufacturing method, polyurethane foam forming compositions that include the present composition or the present composition obtained by the above manufacturing method, and polyurethane foams made from these as raw materials.
[0058] The effects of the invention
[0059] According to the manufacturing method of the present invention, a method for manufacturing an improved hydrosilylation reaction process comprising a (AB)n type polyether modified silicone composition can be provided, as well as the use of the composition obtained by the manufacturing method as a foam stabilizer, etc. The (AB)n type polyether modified silicone composition suppresses the influence caused by the quality and batch deviation of raw materials, is low in cost, and is not easily affected by the metering error of raw materials or batch influence (acid value, etc.), can be manufactured stably and easily, has excellent cost utilization and supply, and has sufficient performance in the use of foam stabilizers for polyurethane foams.
[0060] In particular, according to the manufacturing method of the present invention, a (AB)n type polyether modified organosilicon composition can be provided that has the same quality and performance as a foam stabilizer as when using a low-cost glycol ether compound as a raw material as when using a high-cost glycol ether compound with a very low acid value as a raw material. Therefore, it is expected that surfactants and the like (especially foam stabilizers) with high-performance (AB)n type polyether modified organosilicon as the main component can be manufactured stably and in large quantities at low cost, and that they can be widely used in the market.
[0061] Furthermore, according to the foam-reinforcing composition of the present invention, a (AB)n type polyether modified silicone composition can be provided that is stable and easy to manufacture, has excellent cost utilization and supply performance, and has sufficient performance in use as a foaming agent for polyurethane foams, particularly exhibiting foaming properties, bubble reinforcement, bubble control and bubble stability in the same foam system.
[0062] More specifically, according to the present invention, a polyether-polysiloxane block copolymer composition can be provided that excels particularly in microcell formation and foam retention, foaming power, and foam volume, even in various fields such as high-density microporous foams based on mechanical foaming methods, other rigid foams, or flexible foams; exhibits excellent homogeneity or stability of the premix; and also demonstrates excellent compatibility with various components in the emulsion composition for foam formation. Furthermore, a foam stabilizer for polyurethane foams composed of this composition can be provided.
[0063] It should be noted that the composition involved in this invention, by using the aforementioned component (A”), component (B’) and a specific amount of component (N), possesses specifically enhanced surface activity and foam retention ability even for the (AB)n type polyether modified silicone foam stabilizer with low viscosity or relatively low molecular weight. Therefore, it has the advantage of ensuring sufficient performance for practical use even if the C=C / SiH molar ratio is not set close to 1.0 during manufacturing, and making production management easier. Attached Figure Description
[0064] Figure 1 This is a graph showing the relationship between the amount of sodium ions (Na) added relative to BDPG [ppm] and the viscosity change rate of the polyether-polysiloxane block copolymer composition and its target level.
[0065] Figure 2 This is a graph showing the relationship between the sodium ion (Na) content [ppm] in the composition and the foam holding power [cm] of the polyether-polysiloxane block copolymer composition, as well as the target level. Detailed Implementation
[0066] The following describes in detail the manufacturing method of the improved hydrogenation silylation reaction process based on the composition comprising a polyether-polysiloxane block copolymer of the present invention. First, the raw materials used in the manufacture of the composition, including their relationship with the manufacturing process, will be described.
[0067] [Raw Material Composition (a1)]
[0068] Component (a1) is derived from the following general formula (1):
[0069] [Chemical Formula 1]
[0070] YO(C x H 2x O) y -Y
[0071] (In the formula, x is a number from 2 to 4, and y represents the result of (C) x H 2x O)y represents the molecular weight of the polyether moiety, which is in the range of 400 to 5000. Y represents a monovalent hydrocarbon group with 2 to 8 carbon atoms at the end, which has a reactive C=C group. The polyether moiety contains at least one propylene oxide group.
[0072] The polyether represented by the polyether containing alkenyl groups at both ends is provided as a polyether-polysiloxane block copolymer (A') by a hydrosilylation reaction with the component (a2) described later.
[0073] Here, the group Y can be selected from vinyl, allyl, methyl allyl, isoprenyl, hexenyl, octenyl, etc., and is particularly preferred to be allyl and / or methyl allyl. y is preferably composed of (C x H 2x O) y The molecular weight of the polyether portion is in the range of 1500 to 5000, and the mass ratio of ethylene oxide (C2H4O) units constituting the entire polyether portion is preferably in the range of 30% to 80% on average.
[0074] Generally, component (a1) is manufactured by nucleophilic substitution of a polyether with terminal hydroxyl groups and a strong base alkoxide with an alkenyl halide, followed by removal of low-boiling-point substances or byproduct salts. In this reaction, the hydroxyl group capping is often incomplete, typically containing a certain amount of impurity hydroxyl groups in group Y. The capping rate is preferably 90 mol% or more, more preferably 95 mol% or more, and particularly preferably 98 mol% or more.
[0075] The water content in component (a1) is preferably 0.5 wt.% or less, more preferably 0.2 wt.% or less, and particularly preferably 0.1 wt.% or less. Since component (a1) is hygroscopic, it may be dehydrated in the reactor before the hydrosilylation reaction begins, depending on the circumstances.
[0076] In addition, component (a1) is prone to oxidative degradation. Therefore, an antioxidant of approximately 100–1000 ppm can be added after the synthesis reaction of component (a1) is completed to dissolve it in the raw materials. A preferred antioxidant is vitamin E.
[0077] [Ingredients (N+S)]
[0078] The component (N+S) is a characteristic feature of the manufacturing method of the present invention, particularly a buffer system that neutralizes trace amounts of acidic components from the raw material component (B') and other raw materials described later. This suppresses side reactions during the manufacture of the polyether-polysiloxane block copolymer (A'), enabling the stable and efficient production of a composition / foaming agent primarily composed of the copolymer (A') or (A') and (B') of the desired design and quality. On the other hand, the buffer system requires that the amount of component (B') used is within 40 to 80 parts by weight relative to the total of 100 parts by weight of component (a1), component (a2) described later, and component (B'), and that the amount of component (N) described later is within 3.8 to 43 wt.ppm relative to the actual amount of (B') used, calculated using sodium ions. There are cases where the above conditions are not met, or where the objectives of the present invention cannot be sufficiently achieved even when using other buffers.
[0079] Furthermore, in the manufacturing method according to the present invention, a particularly preferred method is characterized by the sodium content in the composition being in the range of 0.6 to 6.7 wt.ppm relative to the total composition. This is because, within this range, in addition to manufacturing advantages, the foam-enhancing effect described later can also be achieved.
[0080] More specifically, the component (N+S) is a sodium salt solution containing sodium monovalent carboxylate with 2 to 18 carbon atoms (N) and one or more solvents selected from water (S1) and monobasic saturated alcohol with 1 to 4 carbon atoms (S2).
[0081] The component (N) is a sodium monovalent carboxylate salt with 2 to 18 carbon atoms, preferably selected from one or more sodium monovalent carboxylate salts with 2 to 8 carbon atoms, and particularly preferably selected from one or more sodium monovalent carboxylate salts with 2 to 4 carbon atoms. Examples of such components include sodium acetate, sodium propionate, and sodium butyrate, with sodium acetate being the most preferred.
[0082] Component (S) is a solvent for component (N) and is one or more liquid compounds selected from (S1) water and (S2) monohydric saturated alcohols having 1 to 4 carbon atoms. By using component (S), sodium salts containing counteranions can be uniformly and easily added to and dispersed in the system. It should be noted that component (S) preferably has excellent solubility, compatibility with other components, and safety, and can be a mixture of two or more components selected from (S1) and (S2).
[0083] (S1) is water, preferably water with few impurities such as ion-exchange water, pure water, ultrapure water, refined water, distilled water, and tap water.
[0084] Specific examples of (S2) include methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol. From the viewpoint of salt solubility, methanol or ethanol is preferred; from the viewpoint of safety, ethanol or isopropanol is preferred.
[0085] The concentration of sodium (N)carboxylate in the sodium salt solution of the raw material component (N+S) varies depending on the solubility of the salt in the solvent used, but practically it can be in the range of 0.5 to 20 wt.%, preferably 1 to 10 wt.%. Water (S1) is often a good solvent for monovalent sodium carboxylate with 2 to 18 carbon atoms, and depending on the type of salt, it can sometimes be dissolved at a concentration of 30 wt.% or higher. Such high-concentration solutions can also be used directly, but the amount added as a solution is relatively small, so the influence of measurement error needs to be considered. Furthermore, whether it can be quantitatively added to the raw material system without loss is also important; measures or considerations are needed to prevent stagnation in the loading line. Alternatively, the preparation of the raw material component (N+S) can be carried out by first preparing a high-concentration aqueous solution, and then diluting it with an appropriate amount of saturated monohydric alcohol (S2) with 1 to 4 carbon atoms.
[0086] A sodium salt solution containing component (S) is mixed into a raw material system containing at least component (a1). This achieves a uniform and fine dispersion compared to mixing component (N) into the raw material system in the form of solid particles, and effectively neutralizes acid impurities from the raw material system (especially component (B') described later). Furthermore, it offers advantages in terms of the appearance (transparency) of the product system after the hydrosilylation reaction, reducing the burden on subsequent filtration and purification processes.
[0087] In this invention, in the process following the addition of component (N) to the system, for the purpose of preventing side reactions, component (S) is removed from the system by known means of heating and / or depressurization, such as stripping, before the start of the hydrosilylation reaction. The mixture after removing component (S) contains at least the aforementioned raw material component (N) and component (a1), wherein component (N) is in a uniform and finely dispersed form in the mixture.
[0088] [Raw Material Composition (a2)]
[0089] Component (a2) is an organopolysiloxane represented by general formula (2) with SiH groups at both ends.
[0090] General formula (2):
[0091] [Chemical Formula 2]
[0092]
[0093] (In the formula, R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have an aliphatic unsaturated bond, and a represents a number from 1 to 200), the polyether-polysiloxane block copolymer (A') is provided by a hydrosilylation reaction with the component (a1).
[0094] Here, R is particularly preferred to be methyl. In addition, from the viewpoint of the usefulness and operability of the manufactured foaming agent, in the above general formula (5), a is preferably a number in the range of 10 to 45.
[0095] Component (a2) is typically manufactured by loading an organosiloxane containing SiH groups at both ends and a low-molecular-weight cyclic organosiloxane in a desired molar ratio, polymerizing them in the presence of an acid catalyst, neutralizing the catalyst after reaching equilibrium, and removing neutralizing salts, etc. In terms of the nature of the equilibrium reaction, the resulting system generally contains, in addition to the target organopolysiloxane containing SiH groups at both ends, 10–15 wt.% of a low-molecular-weight cyclic organosiloxane.
[0096] Here, when using the polyether-polysiloxane block copolymer composition of the present invention as a foam stabilizer for low VOC / emission polyurethane foam, it is preferable that the composition does not substantially contain low molecular weight siloxanes with 20 or fewer silicon atoms.
[0097] On the other hand, in the manufacturing method of this composition, production efficiency is significantly improved when there is substantially no stripping step after the synthesis of the copolymer (i.e., after the hydrosilylation reaction). In particular, the stripping step after the synthesis of the copolymer is prone to causing severe foaming accompanied by depressurization, and therefore is preferably avoided. Therefore, it is preferable to remove low molecular weight siloxanes, especially low molecular weight cyclic siloxanes, from component (a2) beforehand. There are many methods for removing low molecular weight siloxanes from component (a2). For example, there are methods that involve blowing small amounts of inert gas such as argon or nitrogen into an equilibrium mixture of organopolysiloxanes containing SiH groups while processing it under high temperature and high vacuum; methods that involve thinning the equilibrium mixture of organopolysiloxanes containing SiH groups into a thin film and stripping it under reduced pressure (e.g., less than 0.5 mm) and heating conditions (50–130 °C); and methods that involve adding an organic solvent that dissolves low-molecular-weight siloxanes but not high-molecular-weight siloxanes, such as methanol, ethanol, or acetone, to the equilibrium mixture of organopolysiloxanes containing SiH groups to extract and remove the low-molecular-weight siloxanes.
[0098] Specifically, in component (a2), the total content of low-molecular-weight cyclic siloxanes with 6 or fewer silicon atoms is preferably 3000 ppm (by weight) or less, and particularly preferably 300 ppm (by weight) or less. For example, a cyclic dimethylsiloxane represented by the formula [(CH3)2SiO]n (where n is an integer from 3 to 10) is a representative cyclic dimethylsiloxane. It should be noted that the content of low-molecular-weight siloxanes in component (a2) can be determined, for example, by diluting component (a2) with an organic solvent and then analyzing the diluted solution using a gas chromatograph.
[0099] [Ingredient (B')]
[0100] Component (B') is one or more glycol ether compounds, characterized in that the terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and other terminals have secondary alcoholic hydroxyl groups, the number of repeating olefinic units having 2 to 4 carbon atoms is in the range of 1 to 3, and it does not contain heteroatoms other than oxygen. In the manufacturing method according to the present invention, component (B') is introduced into the composition as a solvent in the synthesis reaction of component (A'), and has the function of improving the workability of the composition, i.e., the foaming agent, or the compatibility with other components used in polyurethane foam formulations.
[0101] Component (B') is preferably a monohydric organic compound having a boiling point capable of distillation or distillation-based purification. Examples of such compounds include one or more glycol ethers selected from propylene glycol monobutyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monobutyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, propylene glycol monopropyl ether, dipropylene glycol monopropyl ether, tripropylene glycol monopropyl ether, propylene glycol monoethyl ether, dipropylene glycol monoethyl ether, and tripropylene glycol monoethyl ether. Particularly preferred are one or more glycol ethers selected from dipropylene glycol monobutyl ether and tripropylene glycol monobutyl ether.
[0102] In the manufacturing method according to the present invention, when using a single glycol ether, it is desirable that its purity is at least 90 wt.%. Preferably, the purity is 95 wt.% or higher, and particularly preferably 98.5 wt.% or higher. When multiple glycol ethers are used simultaneously as raw material (iv), the purity of each glycol ether is also preferably high, as described above.
[0103] Furthermore, as mentioned above, component (B') may sometimes contain trace amounts of acidic substances due to factors such as the manufacturer or storage conditions. The content of acidic substances in component (B') is preferably 0.02 wt.% or less, more preferably 0.01 wt.% or less, and particularly preferably 0.001 wt.% or less.
[0104] The water content in component (B') is preferably 0.5 wt.% or less, more preferably 0.2 wt.% or less, and particularly preferably 0.1 wt.% or less. Component (B') is hygroscopic; therefore, depending on the circumstances, it may be dehydrated in the reactor before the start of the hydrosilylation reaction.
[0105] In the composition obtained by the manufacturing method according to the present invention, the mass ratio of component (A') to component (B') is in the range of 20:80 to 60:40. Therefore, it is important to use component (B') in an amount of 40 to 80 parts by weight relative to a total of 100 parts by weight of components (a1), (a2), and (B') as raw materials, considering the performance, quality, ease of use, and operability of the composition.
[0106] [Raw material composition: Hydrosilylation reaction catalyst]
[0107] In the manufacturing method of this invention, the aforementioned components (a1) and (a2) are reacted by a hydrosilylation reaction to form component (A') in the presence of an effective amount of hydrosilylation reaction catalyst. Here, the hydrosilylation reaction catalyst is not limited to any specific catalyst, as long as it can promote the hydrosilylation reaction; it can be appropriately selected from known hydrosilylation reaction catalysts for use in this invention. Specific examples of hydrosilylation reaction catalysts include particulate platinum, chloroplatinic acid, alcohol-modified chloroplatinic acid, olefinic complexes of chloroplatinic acid, coordination compounds of chloroplatinic acid and vinylsiloxanes, platinum black, and other platinum-containing hydrosilylation reaction catalysts adsorbed on silica micropowder or carbon powder supports.
[0108] In the manufacturing method of the present invention, a neutral platinum complex catalyst is particularly preferred for the hydrosilylation reaction, and 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex is particularly preferred. On the other hand, when using acidic hydrosilylation reaction catalysts such as chloroplatinic acid or alcohol-modified chloroplatinic acid, it is sometimes necessary to use or increase the amount of (N) specific monovalent carboxylic acid sodium salt or other buffers that constitute the buffer system.
[0109] The amount of hydrosilylation catalyst used is an effective amount and is not particularly limited. However, when the total mass of components (a1) and (a2) is set to 100% by mass, the amount of metal atoms (especially platinum group metal atoms) in the hydrosilylation catalyst is 0.1 to 200 ppm by mass, preferably in the range of 1 to 50 ppm. This is because when the content of the hydrosilylation catalyst is less than the lower limit, the copolymerization reaction based on the hydrosilylation reaction sometimes becomes insufficient; when it exceeds the upper limit, it is uneconomical and sometimes adversely affects the transparency, such as the coloring, of the resulting composition.
[0110] [Ingredients: Antioxidants]
[0111] The polyether-polysiloxane block copolymer compositions involved in this invention can sometimes deteriorate due to gradual oxidation by oxygen in the air. To prevent this, antioxidants such as phenolic, hydroquinone, benzoquinone, aromatic amine, or vitamin-based antioxidants can be added to improve oxidative stability. Examples of such antioxidants include BHT (2,6-di-tert-butyl-p-cresol) and vitamin E.
[0112] For the sum of 100 parts by weight of components (A'), (B'), and optional component (C), the antioxidant preferably contains 1 to 1000 wt.ppm, more preferably 50 to 500 ppm.
[0113] In the manufacturing method of the present invention, the antioxidant is added to the manufacturing raw material system at any time, either before or after the hydrosilylation reaction, but it is particularly preferred to add it together with the component (a1) in an amount within the range described above.
[0114] [Ingredients: Other buffers]
[0115] In the manufacturing method of the present invention, the buffer system is a sodium carboxylate solution as the component (N+S), but additional ingredients selected from [other sources] may be added as desired.
[0116] (K) potassium salts composed solely of carbon, hydrogen, and oxygen, with 1 to 8 carbon atoms, and possessing a monovalent counter anion that does not contain a benzene ring structure.
[0117] And buffers in other alkali metal salts or alkaline earth metal salts.
[0118] As an example, potassium salts that can serve as other buffers include potassium carbonate, potassium benzoate, potassium lactate, potassium laurate, potassium oleate, potassium bicarbonate, potassium acetate, potassium propionate, potassium butyrate, potassium isobutyrate, potassium 2-ethylhexanoate, etc., but are not limited to these.
[0119] When adding a buffer, it is preferable to prepare the buffer in the composition as a buffer solution dissolved or dispersed in water and / or a monohydric saturated alcohol having 1 to 4 carbon atoms, either together with or separately from component (N). It should be noted that the buffer can be used in solid form, provided it does not impair the technical effects of the invention.
[0120] [Ingredients: Other neutralizing agents]
[0121] In the manufacturing method of the present invention, an appropriate amount of a neutralizing agent is added together with the sodium salt solution, which is the component (N+S).
[0122] From (M) the following general formula:
[0123] [Chemical Formula 3]
[0124]
[0125] (In the formula, R' represents a monovalent hydrocarbon group with 1 to 18 carbon atoms, R” represents methyl or ethyl, p represents a number from 0 to 20, q represents a number from 1 to 20, and the bonding mode between the (poly)oxyethylene part and another (poly)oxyene part can be random or block.)
[0126] The compound represented is a (poly)oxyolefin tertiary amine compound.
[0127] Specifically, examples of such (poly)oxyalkylene tertiary amine compounds include tertiary amine compounds represented by the average molecular formula R'N[(CH2CH2O)4{CH2CH(CH3)O}4H]2 (R' = coconut alkyl).
[0128] These buffers (including their dissolving or dispersing solvents) or neutralizing agents can be added to the manufacturing raw material system without impairing the technical effects of the manufacturing method involved in this invention. In addition to the sodium salt solution as the aforementioned component (N+S), the above-mentioned buffers or neutralizing agents are used to carry out the hydrosilylation reaction in their presence. By neutralizing acidic substances in the manufacturing raw material system, the quality effects from components (B') and the like can sometimes be further reduced. Furthermore, depending on the type of additive, a foam-enhancing effect can sometimes be achieved in the final composition.
[0129] [Ingredient(A')]
[0130] The manufacturing method of this invention is an improved hydrosilylation reaction process for components (a1) and (a2), providing a composition comprising a polyether-polysiloxane block copolymer (A') with a specific structure. Component (A') synthesized by this manufacturing method is a main agent such as a surfactant, and is particularly suitable for use as a foam stabilizer for polyurethane foams.
[0131] Component (A') is one of the main components of this composition, and has intramolecular properties.
[0132] From general formula (3):
[0133] [Chemical Formula 4]
[0134]
[0135] The structural unit represented is a polyether-polysiloxane block copolymer.
[0136] As long as the above structure is satisfied, there are no particular restrictions on the terminal groups of component (A'), but in the case of synthesis via the hydrosilylation reaction described later, the structure of its molecular chain end is preferably selected from Z. 1 : Alkenyl, hydroxyl, alkoxy, or acetoxy groups that are partially bonded to the polyether; and
[0137] Z 2 Monovalent hydrocarbon groups, hydroxyl groups, alkoxy groups, C1-C8 alkylene oxide groups, or hydrogen groups bonded to silicon atoms and without heteroatoms.
[0138] One or more functional groups in it.
[0139] In the formula, R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have an aliphatic unsaturated bond, exemplified by an alkyl group with 1 to 9 carbon atoms. Methyl is particularly preferred industrially. Y' is a divalent hydrocarbon group with 2 to 8 carbon atoms that is bonded to an adjacent silicon atom via a carbon-silicon bond and to a polyoxyethylene block via an oxygen atom, preferably a divalent hydrocarbon group with 3 to 4 carbon atoms, and particularly preferably isobutylene.
[0140] a is a number from 1 to 200, x is a number from 2 to 4, and y represents the result of (C) x H 2x O)y represents a polyether moiety with a molecular weight in the range of 400 to 5000, the polyether moiety containing at least one propylene oxide group, and n being a number of at least 2.
[0141] From the viewpoint of its usefulness as a foam stabilizer and the stability of the copolymer, the single or double ends of the polyether-polysiloxane block copolymer as component (A') are preferably capped by functional groups containing the polyether moiety. In this case, the terminal groups are preferably those of Z. 1 The alkenyl, hydroxyl, alkoxy, or acetoxy group, which is represented and partially bonded to the polyether, is particularly preferably methylallyl. It should be noted that when an organopolysiloxane containing SiH groups at both ends is used as the raw material for component (A'), a portion of the terminal SiH may sometimes react with the hydroxyl group of component (B') described later, and a portion of its terminal group may also become a residue from the glycol ether of (B').
[0142] On the other hand, the terminal groups of component (A') preferably do not contain reactive functional groups having heteroatoms, and particularly preferably do not contain reactive functional groups that are ring-opening reactive as epoxy groups or amine groups.
[0143] The average molecular weight of the copolymer can be designed by adjusting the molar ratio (reaction ratio) of the organopolysiloxane containing SiH groups at both ends and the polyether containing alkenyl groups at both ends, which is used as its raw material. Furthermore, surface activity and affinity for polyurethane foam systems can be easily controlled by adjusting the EO% or size of the polyether portion, or by introducing hydroxyl or hydrophobic groups into the copolymer ends. Therefore, this copolymer composition performs excellently as a surfactant for bubble control or bubble stabilization in various types of polyurethane foam formulations.
[0144] [Features of specially selected ingredients (A”) and unique foam-enhancing effects, etc.]
[0145] From the viewpoint of usefulness and operability as a foaming agent, in the above general formula (3), it is particularly preferred that a is a number in the range of 10 to 45, y is a number in the range of 1500 to 5000 in molecular weight of the polyether (polyoxyethylene) portion, and the mass ratio of ethylene oxide (C2H4O) units constituting the polyether portion as a whole is in the range of 30 to 80% on average. In the present invention, the polyether-polysiloxane block copolymer having a structure that satisfies the above conditions in general formula (3) is referred to as component (A”) as a particularly preferred embodiment.
[0146] Within the aforementioned range, the hydrophilicity of the polyether-polysiloxane block copolymer is well balanced, and it necessarily contains a certain amount of propylene oxide units or butene oxide units. Therefore, the compatibility between the polyol or isocyanate, which is the main component of the polyurethane foam forming composition, and the foam stabilizer is improved, which is beneficial for achieving the desired foam-stabilizing effect based on the improved stability of the premix. The function as a surfactant or foam stabilizer, as well as the workability during or after synthesis, are also improved.
[0147] Furthermore, in compositions comprising a polyether-polysiloxane block copolymer having a preferred structure (A”), said component (B”), and component (N), further advantages such as foam reinforcement can sometimes be obtained when the components satisfy a limited quantity relationship.
[0148] Specifically, compositions containing components (A”) and (B’) in a mass ratio of component (A”): component (B’) = 20–60: 80–40 (here, the total amount of component (A”) and component (B’) is set to 100) and further containing sodium salts of monovalent carboxylic acids having 2–18 carbon atoms as component (N) in a sodium conversion range of 0.6–6.7 wt.ppm relative to the total amount of component (A”) and component (B’), exhibit exceptionally enhanced surface activity / foam retention capacity and are extremely useful as surfactants, foam stabilizers for polyurethane foams, or components of premixes for polyurethane foams.
[0149] [Manufacturing method of the present invention: steps 1 to 4]
[0150] The manufacturing method of the present invention requires steps 1 to 3 as essential steps, and may also include an optional filtration step (step 4). In particular, from the viewpoint of industrial productivity and ensuring the quality of the obtained composition, these steps 1 to 3 are especially preferably carried out in a reaction vessel in the manufacturing method of the present invention.
[0151] [Process 1: Mixing of raw materials]
[0152] Step 1 is a process of mixing a raw material component comprising at least a polyether containing alkenyl groups at both ends as the raw material component (a1) and a sodium salt solution as the component (N+S). By using component (S), the sodium salt of component (N) is uniformly and finely dispersed in the raw material component (a1), effectively neutralizing acid impurities from the raw material system involved in this invention (especially the raw material component (B') described later). Furthermore, it is advantageous in terms of the appearance (transparency) of the product system after the hydrosilylation reaction, and it also reduces the burden on subsequent filtration and purification processes. The mixing method in Step 1 is not particularly limited as long as it can achieve uniform mixing; mechanical mixing / stirring methods such as mixers and stirring blades are convenient.
[0153] Here, step 1 can be a process of mixing the stated component (a1), the stated component (N+S), and one or more other raw material components selected arbitrarily. For example, component (a1) and the antioxidant can be mixed beforehand and then mixed together with component (N+S), or components (a1), component (a2), component (B'), component (N+S), antioxidants, and other additives can be mixed beforehand; there are no particular limitations in the manufacturing method of the present invention. Preferably, component (a2) is not allowed to coexist with the hydrogen silylation reaction catalyst in step 1. This is because unintended forms of hydrogen silylation reaction or side reactions can easily occur in steps 1 and 2. Therefore, in step 1, it is preferable that the input of component (a2) and the hydrogen silylation reaction catalyst into the raw material system is selective, and it is particularly preferable that the hydrogen silylation reaction catalyst is not added to the raw material system in step 1. It should be noted that if the hydrogen silylation catalyst has excellent compatibility with component (a1) and will not be deactivated by contact with component (N+S), the catalyst can be dissolved in component (a1) for use. However, if this is not the case, it will cause scum formation due to catalyst aggregation or a decrease in reaction efficiency, so caution is required.
[0154] It should be noted that the composition of other raw materials needs to be changed depending on the raw material composition mixed in step 1. For example, if only component (a1), component (N+S), and antioxidant are mixed in step 1, and the solvent (S) is removed in step 2 (described later), the mixture after removing component (S) is a mixture of component (a1), component (N), and antioxidant. Therefore, other raw material components (a2), component (B'), and the hydrosilylation catalyst are further added to this mixture to carry out the hydrosilylation reaction in step 3. On the other hand, when step 1 is a mixture containing all raw material components except the hydrosilylation catalyst, the hydrosilylation reaction in step 3 can be carried out by adding only the unadded hydrosilylation catalyst to the mixture after removing component (S).
[0155] [Step 2: Solvent (S) Removal Step]
[0156] Step 2 is a subsequent step after Step 1. It involves removing the solvent component (S) from the system using known methods such as stripping, accompanied by heating and / or reduced pressure, to prevent side reactions. Without removing the component (S) from the raw material through Step 2, it is sometimes impossible to solve the technical problem of preventing side reactions in the hydrosilylation process when using inexpensive and low-purity raw material components (B'). It should be noted that the mixture after removing component (S) contains at least the aforementioned raw material component (N) and component (a1), with component (N) being uniformly and finely dispersed in the mixture.
[0157] [Process 3: Hydrosilylation Reaction]
[0158] Step 3 is characterized by including a step of carrying out a hydrosilylation reaction in the presence of a mixture containing raw material component (N) and component (a1) obtained in step 2, said component (a2), a solution containing said component (B'), and a hydrosilylation reaction catalyst (wherein, when the total amount of components (a1), components (a2), and component (B') is set to 100 parts by weight, the amount of component (B') used is in the range of 40 to 80 parts by weight, and relative to the amount of component (B') used, the sodium cation (Na) in component (N) is... + The content of (N) is in the range of 3.8 to 43 wt.ppm. Here, the amount of component (N) used is particularly preferred to be such that sodium cations (Na) are used. + The content of (A') relative to the total amount of components (a1), (a2), and (B') is in the range of 0.6 to 6.7 wt.ppm. Through this hydrosilylation reaction process, (A') with the above general formula (3) was synthesized:
[0159] [Chemical Formula 5]
[0160]
[0161] The structural unit represented is a polyether-polysiloxane block copolymer. In this invention, it is particularly preferred to obtain a polyether-polysiloxane block copolymer (A”) having a structure in general formula (3) that satisfies the conditions described above.
[0162] In the hydrosilylation reaction process involved in this invention, the amount of terminal alkenyl groups (R-Vi) in component (a1) is preferably equal to or slightly excess relative to the amount of silicon atoms bonded to hydrogen atoms (Si-H) in component (a2). More specifically, the molar ratio (ratio) of [R-Vi] / [Si-H] is preferably 1.0 to 1.5, and particularly preferably in the range of 1.1 to 1.2.
[0163] As described in Patent Document 6 (International Publication No. 2016 / 166979), generally speaking, the suitability of the polyether-containing silicone as a foaming agent is related to the type of foaming resin, and when arranged in order from suitable for low molecular weight foams to suitable for high molecular weight foams,
[0164] It becomes a highly elastic foam < rigid foam < soft foam < microporous foam.
[0165] Furthermore, the structure of the polyether moiety also significantly influences the size of the foam. Therefore, when aiming to reduce air permeability by decreasing cell size, a polyether structure with a high EO content is chosen; when aiming to stabilize / retain bubbles, a polyether with a large molecular weight is chosen, thus expanding the processing range. To ensure suitability for a wide range of applications / formulations, methods such as using multiple polyethers with different molecular weights or structures in the raw materials to expand the molecular weight distribution of the polyether moiety can also be applied in the polyether-polysiloxane block copolymer composition and its manufacturing method involved in this invention. Additionally, since polyols, as one of the main raw materials for polyurethane, have PPG structural units, from the viewpoint of compatibility in foam formulations, it is often desirable for the polyether moiety in polyether-modified silicone to also contain PO (propylene oxide) chains.
[0166] The requirements for the foam stabilizer vary depending on the type of polyurethane foam formulated with the (AB)n type polyether modified organosilicon composition involved in this invention. However, since the chain length of organopolysiloxane (a2) with SiH groups at both ends represented by the general formula (2), or the type of polyether (a1) with alkenyl groups at both ends represented by the general formula (1), the reaction ratio or mass ratio of these can be appropriately adjusted, or the surface activity or affinity with the polyurethane foam system can be controlled according to the EO / PO% or molecular weight of the polyether portion, the preferred foam stabilizer can be freely designed according to the desired outcome.
[0167] The hydrosilylation reaction conditions involved in this invention can be arbitrarily selected, but can be obtained by adding a small amount of antioxidants such as tocopherol (vitamin E) and heating and stirring at room temperature to 200°C, preferably 50 to 100°C, under an inert gas atmosphere such as nitrogen. It should be noted that the antioxidant can also be added after the hydrosilylation reaction is complete. The reaction time can be selected according to the reaction scale, the amount of catalyst used, and the reaction temperature, generally ranging from several minutes to several hours. Furthermore, the reaction can be carried out under reduced pressure for purposes such as quality improvement; for example, the reaction conditions proposed in Patent Document 4 (Japanese Patent Application Publication No. 11-116670) can be used without particular limitation.
[0168] The endpoint of the hydrosilylation reaction can be confirmed by the disappearance of Si-H bond absorption based on infrared spectroscopy (IR) or by the cessation of hydrogen production through the alkaline decomposition gas generation method described below. It should be noted that the amount of hydrogen produced can also be determined by analyzing the silicon atoms bonded to hydrogen atoms (Si-H) in organopolysiloxanes containing SiH groups at both ends as reactants, using the same method. A summary is provided below.
[0169] <Alkali decomposition gas generation method: A solution of the sample dissolved in toluene or IPA is reacted with a 28.5% (w / w) potassium hydroxide ethanol / water mixture at room temperature. The generated hydrogen gas is collected in a collection tube, and its volume is determined.>
[0170] In the manufacturing method of this composition, it is preferable that there is no stripping step after the step of synthesizing the polyether-polysiloxane block copolymer (A') by hydrosilylation reaction. This is to avoid foaming during the manufacturing process after the synthesis of component (A'). It should be noted that, from the perspective of ease of use and operability, it is preferable that the composition with components (A') and (B') as the main components has a viscosity in the range of 100 to 60,000 mm² / s at 25°C.
[0171] [Process 4: Filtration Process]
[0172] In the manufacturing method of this composition, it is preferable to optionally include a filtration step of the obtained composition after the hydrosilylation reaction. Here, the filter, filter media, and other means used for filtration can be appropriately selected depending on the manufacturing scale, the type or extent of foreign matter, but from the viewpoint of reducing waste, ensuring operator safety, operational efficiency, and ensuring the quality or performance of this composition in its use as a foaming agent, it is preferable to use a Zeta potential adsorption filter, bag filter, cartridge filter, etc. It should be noted that step 4 can be performed at any time before or after the addition of component (C) described later, and can also be performed more than twice depending on the desired light transmittance, etc.
[0173] The above-mentioned filtration process is not particularly limited, but the composition after the hydrogen silanization reaction can be filtered in such a way that the transmittance (580nm) is 90% or more, more preferably 95% or more.
[0174] [Addition of ingredient (C)]
[0175] In the method of manufacturing this composition, the following component (C) may be further added to the composition with the main components (A') and (B') in such a way that the content of component (A') is 1% by mass or more, and then the mixture may be homogenized.
[0176] Component (C) is a polyether compound that is compatible with the synthesized components (A'), (B'), and (N1), and is selected from components (C1) to (C3) below. It has the following advantages: by homogenizing the entire composition, the viscosity and other properties of the composition involved in this invention can be adjusted, improving ease of use and handling (operation) without adversely affecting the function of the composition as a foam stabilizer or surfactant. Furthermore, component (C) can be used, and is preferred, for adjusting the hydroxyl value in the polyurethane foam forming composition containing this composition, i.e., controlling various physical properties such as the crosslinking density or strength of the polyurethane foam. It should be noted that the timing of adding component (C) to the system can be arbitrarily chosen.
[0177] (C1) A polyether alcohol represented by the following general formula (4).
[0178] General formula (4):
[0179] [Chemical Formula 6]
[0180]
[0181] (In the formula, R represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have aliphatic unsaturated bonds, R” represents methyl or ethyl, k satisfies the condition 0≤k≤20, l satisfies the condition 4≤l≤50, and the wt.% of the oxyethylene part of the polyether portion is less than 60%)
[0182] As a preferred example of component (C1), polypropylene glycol n-butyl ether with k=0, R=n-C4H9, and R”=CH3 can be cited, which has the advantages of being easy to handle and readily available at low cost. In particular, polyether monools in the range of 4 ≤ l ≤ 33 have excellent compatibility with the composition and are preferred. Furthermore, when pursuing low VOCs or wanting to reduce the concentration of hydroxyl groups from (C1), polyether monools in the range of 10 ≤ l ≤ 33 are preferred.
[0183] (C2) Polyether diol represented by the following general formula (5).
[0184] General formula (5):
[0185] [Chemical Formula 7]
[0186]
[0187] (In the formula, R” represents the same meaning as described above, k’ satisfies the condition 0≤k’≤10, l’ satisfies the condition 4≤l’≤70, and the wt.% of the ethylene oxide portion of the polyether portion is 30% or less.)
[0188] As a preferred specific example of component (C2), polypropylene glycol with k' = 0 and R” = CH3 can be cited, which has the advantages of being easy to handle and readily available at low cost. In particular, polyether glycols in the range of 4 ≤ l' ≤ 34 have excellent compatibility with the composition and are preferred.
[0189] (C3) The polyether triol is obtained by addition polymerization of 2-4 carbon alkyl esters to glycerol and / or trimethylolpropane, with the wt.% of the ethylene oxide portion of the polyether portion being less than 20 and the average molecular weight in the range of 500 to 4500.
[0190] As a preferred example of component (C3), polyether triols obtained by propylene oxide addition polymerization of glycerols are listed. Polyether triols with an average molecular weight of about 1,500 to 3,500 are easy to handle and have particularly good compatibility with the composition, and are therefore preferred.
[0191] Relative to the composition, component (C) may be contained in a range where the content of component (A') is 1% by mass or more.
[0192] The preferred timing for adding component (C) is after the hydrosilylation reaction, at which point the overall viscosity of the composition containing component (C) is preferably between 100 and 35,000 mm at 25°C. 2The viscosity range can be adjusted by varying the content of components (C), (A'), and (B') to meet the desired properties of the polyurethane foam, thereby homogenizing the mixture. It should be noted that, as already explained, the technical intent of adding component (C) is not limited to adjusting viscosity, etc.
[0193] In compositions in which the mass ratio of component (A') to component (B') is in the range of 20 / 80 to 60 / 40, and further, relative to the actual amount of component (B') used, the amount of sodium carboxylate salt, converted to sodium, is in the range of 3.8 to 43 wt. ppm, the composition further containing component (C) is useful as a foam stabilizer or surfactant, particularly as a foam stabilizer or premix for polyurethane foam.
[0194] In particular, the synthesized component (A') further satisfies the structural characteristics of component (A”), the mass ratio of component (A”) to component (B') is in the range of 20 / 80 to 60 / 40, and it contains a sodium salt of a monovalent carboxylic acid with 2 to 18 carbon atoms in the range of 0.6 to 6.7 wt.ppm relative to the total amount of components (A”) and (B') in the range of 1 to 20 wt%. The resulting composition is particularly useful in the above-mentioned applications, not only because of its manufacturing advantages, but also because it can be expected to produce special technical effects such as foam enhancement.
[0195] [Other optional ingredients]
[0196] The composition obtained by the manufacturing method of the present invention is preferably used primarily as a surfactant, etc., and may also contain other polyether-modified organosilicones, linear organosilicones, organic surfactants, etc., without impairing its technical characteristics. In this case, the content of these is preferably not more than equal in mass to the component (A') in the whole composition. It should be noted that such a composition can also preferably be used as a surfactant, etc., especially as a foaming agent for polyurethane foam.
[0197] In this composition, without impairing the technical effects of the invention, at least a portion of the components that can be used in the polyurethane foam forming composition described later may be added in advance as other optional components.
[0198] In the method for manufacturing this composition, other optional components already described, component (B'), and component (C) may be added, and the mixture may be homogenized. Furthermore, in the method for manufacturing this composition, without impairing the technical effects of the invention, at least a portion of the components usable in the polyurethane foam forming composition described later may be added to this composition as other optional components, and the mixture may be homogenized. This provides the advantage of being able to adjust a homogeneous premix for polyurethane foam containing both a foam stabilizer component and desired components.
[0199] Organic solvents can be used in this composition, but the manufacturing method involved in this invention can avoid the use and mixing of aromatic hydrocarbon solvents such as BTX (benzene, toluene, xylene) solvents, thus meeting the current needs of the polyurethane industry that requires strict VOC / emission management or does not contain BTX, etc.
[0200] [Benefits of this manufacturing method]
[0201] The manufacturing method of this composition utilizes inexpensive raw materials with varying quality and is highly efficient. Even with copolymers designed for high molecular weight or strong foam control, foam control problems arising during the manufacturing process are not caused or can be easily eliminated. Therefore, it offers excellent productivity and comprehensively addresses both manufacturing and quality issues directly related to industrial production costs. Thus, by using the polyether-polysiloxane block copolymer composition obtained through this manufacturing method, it is expected that foam stabilizers containing this composition will achieve sufficient and stable market penetration and can be utilized as high-performance raw materials.
[0202] As described above, the polyether-polysiloxane block copolymer composition of the present invention (comprising the composition obtained by the above manufacturing method) is particularly useful as a foam stabilizer used in the manufacture of polyurethane foam, and can be used directly as a surfactant and a foam stabilizer for polyurethane foam. Alternatively, it can be formulated into a premix for polyurethane foam for system use.
[0203] [Use of this composition]
[0204] The polyether-polysiloxane block copolymer composition of this invention has organosilicon sites and polyether sites with different hydrophilicities within the molecule. Therefore, it can be used without particular limitation in the conventional uses of polyether-polysiloxane block copolymers, and can be used without particular limitation in surfactants, foam stabilizers, fiber lubricants or softeners, surface treatment or coating agents, reactive raw materials for other polymeric materials, etc. In particular, the polyether-polysiloxane block copolymer composition of this invention is useful as an industrial surfactant, and its formulation is not particularly limited to coatings, coating agents, building materials, hydrophilic agents, surface treatment agents, foaming resin compositions, etc. Furthermore, due to its function as a surfactant, it is particularly useful as an additive for coatings, emulsifier, solubilizer, and foam stabilizer for polyurethane foams.
[0205] Particularly suitable uses of the compositions of the present invention are as surfactants, foam stabilizers for polyurethane foams, or premixes for polyurethane foams. Their use as foam stabilizers will be described in more detail below. It should be noted that in this specification, polyurethane foam is sometimes referred to as "polyurethane foam" or simply "foam."
[0206] [Use as a foaming agent]
[0207] As described above, the polyether-polysiloxane block copolymer composition involved in this invention can be manufactured relatively easily and is not easily affected by the quality of raw materials, and has excellent cost utilization. Therefore, it can be preferably used as a surfactant for bubble control or bubble stabilization, especially a foam stabilizer, when manufacturing foaming resins, especially polyurethane foams.
[0208] Especially when used as a foam stabilizer or premix for polyurethane foam, this composition has the following advantages: it is not limited to a simple bubble stabilizer; the control or design of the open cell ratio is easy; the homogeneity or stability of the premix is excellent; in addition, it has excellent compatibility with various components in the emulsion composition for foam forming; and it also has excellent foam stabilization properties in microporous applications or low-resilience foam applications.
[0209] [A composition comprising preferred ingredients (A”), (B’), and (N) and having a foam-enhancing effect]
[0210] The components (A”), (B’), and sodium monovalent carboxylate salts containing the structural features described in general formula (3) and (N) having a carbon number in the range of 2 to 18 are included.
[0211] The mass ratio of component (A”) to component (B’) is in the range of 20:80 to 60:40, and the component (A”) contains sodium cations (Na) from component (N) in the range of 0.6 to 6.7 wt.ppm relative to the sum of components (A”) and (B’). + The composition of N, compared with components (A'), (B'), or in combination with them in a specific mass ratio, significantly improves the foam-enhancing properties of the composition and the foam stabilizer containing it. On the other hand, the amount of component (N) used is critical; when it is outside the range, the technical effects such as sufficient foam enhancement cannot always be achieved. Specifically, in order to achieve foam enhancement, component (N), as a sodium salt, needs to be used in combination with components (A') and (B') having preferred structural characteristics. When its amount is below the lower limit, the foam enhancement sometimes becomes insufficient, and when it exceeds the upper limit, it exceeds the limit of the compatibility balance of the formulation system, and the component tends to precipitate in the system, sometimes failing to exhibit sufficient foam enhancement.
[0212] The method for obtaining the foam-enhancing composition according to the present invention can be the same as described above, provided that the amount of component (N) used is limited to the range described above and the raw material components (a1) and (a2) that provide component (A”) are used. This method is preferred, but not limited to. For example, when adding component (N), in step 1, component (S) can be added to the manufacturing raw material system by dispersing it in a solvent (S3) of one or more liquid compounds selected from saturated diol compounds with 3 to 9 carbon atoms (e.g., propylene glycol). In this case, the removal step of component (S) in step 2 can be omitted, and the remaining raw material component can be added in the state of residual solvent (S3) for a hydrosilylation reaction. That is, the method for obtaining the foam-enhancing composition described above can be a method that does not require steps 1 to 3 as described above. As long as the above-described structure of the components is satisfied, the foam-enhancing composition according to the present invention does not need to be determined by the manufacturing method.
[0213] [Polyurethane foam forming compositions comprising this composition and polyurethane foams]
[0214] The types, properties, and applicable formulations of polyurethane foams and polyurethane foams involved in this invention are not limited as long as they contain the polyether-polysiloxane block copolymer composition of this invention (including the composition obtained by the above manufacturing method) or are used as at least a part of the raw materials.
[0215] Generally, polyurethane foams are classified into rigid polyurethane foams and flexible polyurethane foams. More specifically, they can be broadly categorized into flexible polyurethane foams, high-elasticity polyurethane foams, rigid polyurethane foams, and specialty foams. For details on these, please refer, for example, to Patent Document 6 (International Publication No. 2016 / 166979). The compositions and foam stabilizers involved in this invention are universal and can achieve excellent effects or industrial production benefits even when formulated into various polyurethane foam formulations.
[0216] Furthermore, as mentioned above, the compositions and foam stabilizers involved in this invention are readily free of BTX solvent, enabling inexpensive and large-scale production, and are therefore suitable for obtaining low-VOC / emission polyurethane foams. Additionally, they facilitate the manufacture of BTX-free foams or premixed systems by foam manufacturers or foam formulation (system) designers. It should be noted that, in order to produce polyurethane foams with low VOC / emissions or low odor, it is preferable to add a non-volatile antioxidant to the polyol described later.
[0217] The polyether-polysiloxane block copolymer composition obtained by the manufacturing method of the present invention is preferably used as a raw material in a polyurethane foam forming composition comprising the following components: (d) foam stabilizer.
[0218] (a) Polyols;
[0219] (b) Polyisocyanates;
[0220] (c) Catalyst;
[0221] (d) foam stabilizers; and
[0222] (e) Optionally selected from the group consisting of foaming agents, foaming agents, diluents, chain extenders, crosslinking agents, water, non-aqueous foaming agents, fillers, reinforcing agents, pigments, dyes, colorants, flame retardants, antioxidants, anti-ozone agents, UV stabilizers, antistatic agents, bactericides, and antimicrobial agents, other than component (d).
[0223] Regarding the raw material composition and its amount used in polyurethane foam forming compositions other than the foaming agent mentioned above (d), raw materials known in the art can be selected, for example, the components described in Patent Document 6 (International Publication No. 2016 / 166979).
[0224] It should be noted that the composition involved in this invention can be used as a foam stabilizer suitable for most polyurethane foams. The formulation amount is such that, relative to 100 parts by weight of (a) polyol, the (A') polyether-polysiloxane block copolymer in the composition ranges from 0.1 to 10 parts by weight, preferably from 0.5 to 5 parts by weight, and more preferably from 1.0 to 3.0 parts by weight.
[0225] The polyurethane foam obtained using the "composition comprising polyether-polysiloxane block copolymer (A')" as described in this invention can be rigid foam, semi-rigid foam, flexible foam, low-resilience foam, HR foam, or microporous foam. For details regarding these and their manufacturing processes, please refer, for example, to Patent Document 6 (International Publication No. 2016 / 166979). These polyurethane foams can be obtained by replacing at least a portion or all of the foaming agent described in Patent Document 6 with the composition described in this invention. Furthermore, in the manufacturing methods of foam stabilizers or polyether-polysiloxane block copolymer compositions described in the examples / comparative examples of Patent Document 3 (Japanese Patent Application Publication No. 08-156143) or International Publication No. 2021 / 131378, by adding and utilizing the method obtained in this invention [for example, by adding an appropriate amount of the (N) component of this invention before the reaction and then allowing it to react], it is possible to arbitrarily enhance the foam properties of various polyurethane foams or adjust the cell size.
[0226] Furthermore, individual methods for manufacturing polyurethane foam can be appropriately selected, but particularly in the detailed descriptions and examples of the polyurethane foam manufacturing methods described in the following patent publications or patent publications, the "composition containing polyether-polysiloxane block copolymer (A')" obtained by the manufacturing method of the present invention can be appropriately applied by replacing silicone-based foam stabilizers or silicone surfactants and silicone copolymer surfactants, and can contribute to the low VOC / emission reduction of the foam. It should be noted that these detailed descriptions or examples include disclosures related to the manufacturing apparatus, and some components can be further replaced by ordinary design changes by those skilled in the art, and the manufacturing conditions can be appropriately changed according to changes in viscosity, etc.
[0227] • US Patent No. 7,825,205 (Japanese Patent No. 5,422,115)
[0228] Japanese Patent Application Publication No. 2014-210832
[0229] Japanese Patent Application Publication No. 07-090102
[0230] • Patent document 3 (Japanese Patent Application Publication No. 08-156143) and Japanese Patent Publication No. 57-014797
[0231] • Patent document 6 (International Publication No. 2016 / 166979)
[0232] Methods for manufacturing polyurethane foam as described in Japanese Patent Publication Nos. 2005-534770, 2005-534770, and 2010-535931;
[0233] The manufacturing process of open-cell polyurethane as described in Japanese Patent Publication No. 2010-539280
[0234] Sealing materials containing polyurethane foam as described in Japanese Patent Application Publication No. 2012-246397, Japanese Patent Application Publication No. 2009-265425, etc.
[0235] Manufacturing of polyurethane foam as described in Japanese Patent Application Publication No. 2012-082273, Japanese Patent Application Publication No. 2010-247532, Japanese Patent Application Publication No. 2010-195870, and Japanese Patent Application Publication No. 2002-137234, etc.
[0236] Manufacturing of viscoelastic polyurethane foam as described in Japanese Patent Publication Nos. 2010-500447, 2010-504391, 2010-538126, 2011-528726, and 2013-529702.
[0237] Furthermore, the polyether-polysiloxane block copolymer composition obtained by the manufacturing method of the present invention can be used for any industrial applications known for (AB)n type polyether modified silicone, other than polyurethane foam, such as fiber treatment agents, fabric softeners, coating additives, etc.
[0238] [Disclosure and teachings on the application of the technical elements of this invention to other hydrogenation silylation reaction processes]
[0239] Given their functions, the sodium salt solution involved in this invention and the carboxylates used in the comparative examples described later are expected to provide similar advantageous process effects in similar hydrosilylation reaction processes. Therefore, by referring to the hydrosilylation reaction process according to this invention, using general non-hydrolyzable polyether-modified organosilicon with a structure whose polyether side chains and / or terminal links are branched onto the organopolysiloxane backbone as the main component, the sodium salt solution involved in this invention, or other buffers studied in the comparative examples, in these hydrosilylation reaction processes, it is possible to improve their production efficiency and production costs. Furthermore, in manufacturing these non-hydrolyzable polyether-modified organosilicones, they can be manufactured by mixing an appropriate amount of buffer into the raw material system in the same manner as the sodium salt solution involved in this invention before the start of the hydrosilylation reaction, and then starting the hydrosilylation reaction after removing the solvent from the buffer by stripping or the like. This description in this specification is intended to provide such teaching and guidance.
[0240] Example
[0241] The present invention will be further described in detail below through examples and comparative examples, but the present invention is not limited thereto. It should be noted that in the following compositional formulas, the Me3SiO group (or Me3Si group) is denoted as "M", the Me2SiO group is denoted as "D", and the MeHSiO group is denoted as "M". H The unit obtained by modifying the methyl group in M and D with any substituent is denoted as M. R and D R Additionally, IPA represents isopropanol, MeOH represents methanol, BDPG represents dipropylene glycol monobutyl ether, EO represents ethylene oxide or vinyl oxyethylene, and PO represents propylene oxide or oxypropylene group.
[0242] <Reference Data 1>
[0243] One of the features of the composition and manufacturing method of the present invention is that it mitigates the influence of the quality of the raw materials used, thereby achieving practically sufficient performance. Table 1 shows the supplier-based quality differences in BDPG; BDPG from Company H and Company L differs in purity, moisture content, acid value, etc.
[0244] [Table 1]: Quality differences among BDPG suppliers
[0245] [Table 1]
[0246]
[0247]
[0248] In the following experimental examples, as a raw material component of linear organopolysiloxane-polyether block copolymers, the following were used:
[0249] (a1-1) Based on the average composition CH2=C(CH3)CH2-O(C2H4O) 35 (C3H6O) 27 -CH2-C(CH3)=CH2 represents dimethyl allyl polyether (unsaturation degree 0.67 meq / g, hydroxyl value 0.8 mg-KOH / g).
[0250] (a1-2) Based on the average composition CH2=C(CH3)CH2-O(C2H4O) 35 (C3H6O) 27 -CH2-C(CH3)=CH2 represents dimethyl allyl polyether (unsaturation degree 0.64 meq / g, hydroxyl value 2.1 mg-KOH / g).
[0251] (a1-3) Based on the average composition CH2=C(CH3)CH2-O(C2H4O) 35 (C3H6O) 27 -CH2-C(CH3)=CH2 represents dimethyl allyl polyether (unsaturation degree 0.60 meq / g, hydroxyl value 3.8 mg-KOH / g).
[0252] (a1-4) Based on the average composition CH2=C(CH3)CH2-O(C2H4O) 35 (C3H6O) 27 -CH2-C(CH3)=CH2 represents dimethyl allyl polyether (unsaturation degree 0.63 meq / g, hydroxyl value 0.7 mg-KOH / g).
[0253] (a1-5) Average composition: CH2=C(CH3)CH2-O(C2H4O) 35 (C3H6O) 27 -CH2-C(CH3)=CH2 represents dimethyl allyl polyether (unsaturation degree 0.64 meq / g, hydroxyl value 1.2 mg-KOH / g).
[0254] *Note: (a1-1)~(a1-5) correspond to different batches of raw materials for dimethyl allyl polyether.
[0255] Using (a2-1) from the average composition formula M H D 20 M H Methylhydropolysiloxane
[0256] Catalyst for the hydrosilylation reaction: a ligand solution of a platinum complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane (Pt concentration 0.43 wt%).
[0257] In addition, when using BDPG manufactured by Company H or Company L as (B') component, it is recorded as "(B')BDPG(Company H)" or "(B')BDPG(Company L)".
[0258] [Light transmittance (T%) in each experimental example]
[0259] In the following experimental examples, the transmittance at a wavelength of 580 nm was measured using a spectrophotometer for the transparency (T%) of each obtained composition. The results are presented as T% in the table.
[0260] [Example 1]
[0261] 104.19 g of (a1-3) dimethyl allyl polyether (containing 500 ppm of natural vitamin E) and 0.15 g of a MeOH(S) solution containing 5 wt.% sodium acetate (N) were charged into a 500 mL reactor. The mixture was heated to 60 °C under nitrogen circulation with stirring. After homogeneous mixing, the MeOH was removed from the system by stripping at 60–80 °C and 2 mmHg for 30 minutes in the same reaction vessel. The pressure was restored, and 45.81 g of (a2-1) methylhydropolysiloxane and 150 g of (B') BDPG (L company) were added with stirring. 0.08 mL of hydrosilylation catalyst was further added, and the reaction was carried out at 60–80 °C for 5 hours, resulting in near-complete reaction. Thus, a solution containing at least the average composition of the formula was obtained in a 50:50 ratio.
[0262] [Chemical Formula 8]
[0263]
[0264] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)
[0265] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a generally transparent liquid polyether-polysiloxane block copolymer composition "1619 mm² / s, (25°C)".
[0266] Since the molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.10, it is assumed that the two ends of the copolymer are mainly polyether-terminated (i.e., the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Additionally, some Si-H groups can undergo dehydrogenation condensation with water or alcohols in the system during the reaction; therefore, it is assumed that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1The structure consists of residues such as BDPG. It should be noted that here, the polyether moiety is a random addition of ethylene oxide and propylene oxide. This is also true in Comparative Examples 1-1 to 1-3.
[0267] [Comparative Example 1-1]
[0268] Without stripping to remove MeOH, 0.08 mL of a hydrogen silanization reaction catalyst was added, and the reaction was carried out at 60–90 °C for 6 hours. Otherwise, in the same manner as in Example 1, a translucent to substantially transparent liquid polyether-polysiloxane block copolymer composition “1581 mm² / s, (25 °C)” was obtained.
[0269] [Comparative Examples 1-2]
[0270] 45.81 g of (a2-1) methylhydropolysiloxane, 104.19 g of (a1-3) dimethyl allyl polyether (containing 500 ppm of natural vitamin E), and 150 g of (B') BDPG (L company) were charged into a 500 mL reactor. The mixture was heated to 60 °C under nitrogen atmosphere with stirring. 0.04 mL of hydrosilylation catalyst was added, and the reaction was carried out at 60–80 °C for 3 hours. A small amount of the reaction solution was then collected and confirmed by alkaline decomposition gas generation, indicating that the reaction was largely complete. This yielded a product containing at least the average composition of the following ingredients in a 50:50 ratio:
[0271] [Chemical Formula 9]
[0272]
[0273] (Here, a = 20, x1 = 35, y1 = 27, n < 6)
[0274] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and an opaque liquid polyether-polysiloxane block copolymer composition of BDPG, "931 mm² / s, (25°C)".
[0275] [Comparative Examples 1-3]
[0276] As a raw material, 0.009 g of sodium acetate solid was further added, and the mixture was heated to 56°C under nitrogen atmosphere with stirring. Then, 0.08 mL of hydrosilylation catalyst was added, and the reaction was carried out at 60–80°C for 6 hours. Otherwise, in the same manner as Comparative Examples 1-2, a mixture containing at least the average composition formula was obtained in a 50:50 ratio.
[0277] [Chemical Formula 10]
[0278]
[0279] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)
[0280] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and a semi-transparent liquid polyether-polysiloxane block copolymer composition of BDPG, "1528 mm² / s, (25°C)".
[0281] [Example 2: Reproducibility Confirmation Test of Dimethyl Allyl Polyether from Example 1 When Batches Are Different]
[0282] A 500 mL reactor was charged with 86.19 g of (a1-1) dimethyl allyl polyether (containing 500 ppm of natural vitamin E) and 0.12 g of a MeOH(S) solution containing 5 wt.% sodium acetate (N) (N+S). The mixture was heated to 60 °C under nitrogen atmosphere with stirring. After homogeneous mixing, the MeOH was removed from the system by stripping at 60–80 °C and 3 mmHg for 40 minutes in the same reaction vessel. The pressure was restored, and 38.81 g of (a2-1) methylhydropolysiloxane and 125 g of (B') BDPG (L company) were added with stirring. 0.06 mL of hydrosilylation catalyst was further added, and the reaction was carried out at 60–90 °C for 6 hours, after which the reaction was largely completed. This yielded a solution containing at least the average composition of the formula [missing information - likely a specific compound or ingredient].
[0283] [Chemical Formula 11]
[0284]
[0285] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)
[0286] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a generally transparent liquid polyether-polysiloxane block copolymer composition "1714 mm² / s, (25°C)".
[0287] Since the molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.20, it is assumed that the two ends of the copolymer are mainly polyether-terminated (the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Additionally, some Si-H groups can undergo dehydrogenation condensation with water or alcohols in the system during the reaction; therefore, it is assumed that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1 The structure consists of residues such as BDPG. It should be noted that here, the polyether moiety is a random addition of ethylene oxide and propylene oxide. This is also true in Comparative Example 3 and Comparative Example 4-1.
[0288] [Example 3: Reproducibility Confirmation Test of Example 2]
[0289] Add 86.70 g of (a1-4) dimethyl polyether (containing 500 ppm of natural vitamin E) and 0.12–0.13 g of a MeOH(S) solution containing 5 wt.% sodium acetate (N) to a 500 ml reactor. Heat to 60 °C under nitrogen circulation with stirring. After homogeneous mixing, remove MeOH from the system by stripping at 60–80 °C and 7–8 mmHg for 30 minutes in the same reaction vessel. Restore pressure, and add 38.31 g of (a2-1) methylhydropolysiloxane and 125 g of (B') BDPG (L company) with stirring. Further add 0.06 mL of hydrosilylation catalyst and react at 70–80 °C for 3 hours. The reaction is then confirmed to be complete. This yields a solution containing at least the average composition of the formula [missing information - likely a specific compound or ingredient].
[0290] [Chemical Formula 12]
[0291]
[0292] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)
[0293] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a generally transparent liquid polyether-polysiloxane block copolymer composition "1634 mm² / s, (25°C)".
[0294] Since the molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.15, it is assumed that the ends of the copolymer are mainly polyether-terminated (i.e., the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Additionally, some Si-H groups can undergo dehydrogenation condensation with water or alcohols in the system during the reaction; therefore, it is assumed that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1 The structure consists of residues such as BDPG. It should be noted that, here, the polyether moiety is a random addition of ethylene oxide and propylene oxide.
[0295] [Comparative Example 2]
[0296] In a 1L reactor, 75.25g of (a2-1) methylhydropolysiloxane, 174.75g of (a1-2) dimethyl allyl polyether, 250g of (B') BDPG (H company), and 0.25g of natural vitamin E were charged and heated to 80-90°C with stirring under nitrogen circulation. 0.56g of hydrosilylation catalyst was added, and the reaction was carried out for 2.5 hours. A small amount of the reaction solution was then collected and confirmed by alkaline decomposition gas generation (using an ethanol / water solution of KOH to decompose the remaining Si-H groups, and calculating the reaction rate based on the volume of hydrogen produced). The reaction was confirmed to be complete. Thus, a product containing at least the average composition of the following in a 50:50 ratio was obtained.
[0297] [Chemical Formula 13]
[0298]
[0299] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)
[0300] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a generally transparent liquid polyether-polysiloxane block copolymer composition "1680 mm² / s, (25°C)".
[0301] It should be noted that while the average composition is presented simply, the molar ratio of C=C groups to Si-H groups in the raw materials is C=C / SiH = 1.18. Therefore, the copolymer ends are polyether-terminated (i.e., the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Furthermore, some Si-H groups can undergo dehydrogenation condensation with water or alcohols in the system during the reaction; therefore, it is considered that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1 The structure consists of residues such as BDPG or IPA. It should be noted that, here, the polyether moiety is a random addition of ethylene oxide and propylene oxide.
[0302] [Comparative Example 3: Reproducibility Confirmation Test of Comparative Example 1-1]
[0303] A 500 mL reactor was charged with 38.81 g of (a2-1) methylhydropolysiloxane, 86.19 g of (a1-1) dimethyl allyl polyether (containing 500 ppm of natural vitamin E), 125 g of (B') BDPG (L company), and 0.12–0.13 g of a MeOH(S) solution containing 5 wt.% sodium acetate (N) and (N+S). The mixture was heated to 46 °C under nitrogen atmosphere with stirring. 0.06 mL of a hydrosilylation catalyst was added, and the reaction was carried out at 60–80 °C for 4 hours. A small amount of the reaction solution was then collected and confirmed by alkaline decomposition gas generation, indicating that the reaction was largely complete. This yielded a product containing at least the average composition of the following ingredients in a 50:50 ratio:
[0304] [Chemical Formula 14]
[0305]
[0306] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)
[0307] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a translucent to substantially transparent liquid polyether-polysiloxane block copolymer composition "1533 mm² / s, (25°C)".
[0308] [Comparative Example 4-1: Reproducibility Confirmation Test of Comparative Example 3]
[0309] In a 500 mL reactor, 38.30 g of (a2-1) methylhydropolysiloxane, 86.70 g of (a1-4) dimethyl allyl polyether (containing 500 ppm of natural vitamin E), 125 g of (B') BDPG (L company), and 0.12–0.13 g of a MeOH(S) solution of 5 wt.% sodium acetate (N) were added. The mixture was heated to 51 °C under nitrogen atmosphere with stirring. 0.06 mL of hydrosilylation catalyst was added, and the reaction was carried out at 50–80 °C for 3.5 hours, confirming the completion of the reaction. A translucent to substantially transparent liquid polyether-polysiloxane block copolymer composition with a flow rate of 1383 mm² / s (25 °C) was obtained.
[0310] [Comparative Example 4-2]
[0311] 43.56 g of (a2-1) methylhydropolysiloxane, 81.45 g of (a1-4) dimethyl allyl polyether (containing 500 ppm of natural vitamin E), and 125 g of (B') BDPG (L company) were charged into a 500 mL reactor. The mixture was heated to 45 °C under nitrogen atmosphere with stirring. 0.06 mL of hydrosilylation catalyst was added, and the reaction was carried out at 45–80 °C for 4.5 hours, after which the reaction was largely completed. This yielded a product containing at least the average composition of [a2-1] in a 50:50 ratio.
[0312] [Chemical Formula 15]
[0313]
[0314] (Here, a = 20, x1 = 35, y1 = 27, n > 6)
[0315] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a generally transparent liquid polyether-polysiloxane block copolymer composition “7300cP, (25°C)”.
[0316] [Evaluation criteria in each experiment]
[0317] For the hydrogenation silylation reaction process that provides linear organopolysiloxane-polyether block copolymers, the following evaluation is conducted considering the differences in raw materials and reaction systems.
[0318] Regarding the reactivity of hydrogen silylation (hereinafter, sometimes simply referred to as "reactivity"), Example 1 is evaluated as "acceptable".
[0319] It is rated "good" under conditions of better responsiveness.
[0320] It is rated as "excellent" in cases of particularly outstanding responsiveness.
[0321] In addition, the viscosity (change rate) of the obtained compositions is shown in the table as a percentage for each experimental example (1-3) using the same dimethyl allyl polyether, which was set to "0%" (= baseline). However, Comparative Example 2 was not used as an evaluation object for viscosity change rate because the BDPG source was different.
[0322] [summary]
[0323] A series of experimental results are shown in Table 2. Except for Comparative Example 2 with different BDPG raw materials and Comparative Example 4-2 with different C=C / Vi ratios, for ease of comparison, examples / comparative examples with the same C=C / Vi ratio using the same batch of dimethyl allyl polyether raw materials are summarized in the table.
[0324] First, Examples 1-3 used relatively inexpensive BDPG manufactured by Company L with a slightly higher acid value as a raw material. Even when using any batch of dimethyl allyl polyether raw material, compared with the comparative reference product (Comparative Example 2) which used expensive BDPG manufactured by Company H as a raw material, it was possible to produce polyether-polysiloxane block copolymer compositions with almost comparable reactivity, viscosity, and transparency (i.e., light transmittance T%). That is, it can be seen that by using the manufacturing method involved in this invention, compositions with effectively suppressed side reactions, practically sufficient high viscosity, higher degree of polymerization of the copolymer, closer proximity to the designed structure, and practically sufficient quality were obtained.
[0325] On the other hand, Comparative Example 2 does not contain a buffer or sodium acetate, and roughly corresponds to Reference Example 1-1 of International Publication No. 2016 / 166979 (Patent Document 6). By using BDPG manufactured by H Company, which has a low acid value, high purity, and is expensive, it is possible to obtain a composition with a practical viscosity and appearance, including the molecular weight of the copolymer. However, BDPG manufactured by H Company is expensive, making it difficult to supply this composition to the market at a low price and in a stable manner.
[0326] On the other hand, in comparison with the examples / comparative examples using the same dimethyl allyl polyether raw material and with the same C=C / Vi ratio, the compositions of the examples obtained by the manufacturing method of the present invention exhibit higher viscosity, suppressed side reactions, and excellent transparency compared to the comparative examples. These effects are attributed to the fine dispersion of the buffer component in the raw material and the prior removal of unwanted dispersion media, thus achieving efficient neutralization of acidic substances.
[0327] In contrast, in Comparative Examples 1-1, 2-1, and 3-1, which did not undergo stripping, the viscosity and transparency were inferior to the compositions involved in the examples. In Comparative Example 1-2, which lacked a buffer, or in Comparative Example 1-3, which added solids, the viscosity or transparency was even worse compared to these comparative experiments. Therefore, it is confirmed that without using the manufacturing method of the present invention, the technical effects of the present invention, including the suppression of side reactions, cannot be achieved when using inexpensive BDPG manufactured by L Company. It should be noted that these results are common when the batches of dimethyl allyl polyether raw materials are the same, confirming good reproducibility.
[0328] The purpose of Comparative Example 4-2 is to obtain a high molecular weight (high viscosity) composition even under the unfavorable conditions of using inexpensive BDPG manufactured by L Company and without a buffer by setting the true value of the molar ratio of C=C group to Si-H group of raw materials: C=C / SiH close to 1.0 (0.95 when simply calculated based on the analysis results of each raw material).
[0329] In this experimental example, the composition with the highest viscosity was obtained among a series of experimental examples. However, even compared with each example or Comparative Example 2, which served as a comparative reference, the viscosity was very high, strongly suggesting that the synthesized composition would exhibit large viscosity deviations if this method were used for commercial production. Furthermore, from a production management point of view, it is difficult to design such a strict C=C / SiH ratio based on the raw materials in each production run, leading to problems with industrial productivity and deteriorating production costs. In addition, the results of Comparative Examples 4-2 strongly suggest that even with strict production management, the viscosity of the product can still deviate significantly due to quality variations or metering errors based on each batch of raw materials or storage conditions, as well as minor variations in manufacturing conditions, easily resulting in products that deviate from quality specifications. Therefore, instead of the manufacturing method of the present invention, a production method that strictly manages the true value of C=C / SiH is inappropriate for achieving the goal of supplying the composition to the market at a low price and stably, and there is a strong concern about industrial productivity under the lack of stable quality specifications.
[0330] [Table 2]
[0331]
[0332]
[0333] *) This is a benchmark sample based on BDPG manufactured by Company H, and is not used as an evaluation object for viscosity change rate.
[0334] **) Compared with other experimental examples, the viscosity deviation is large, raising concerns about its stable industrial production performance.
[0335] [Examples 4-1 to 4-3, Example 5, etc.: Effective range of sodium acetate relative to BDPG addition [ppm]]
[0336] To confirm the effective range of sodium acetate addition relative to BDPG [ppm], in the manufacturing method of the present invention, a composition comprising a linear organopolysiloxane-polyether block copolymer is manufactured by varying the amount of sodium acetate added, and the relationship between the amount of sodium acetate added (ppm) and the viscosity of the resulting composition is shown below. Figure 1 It should be noted that, in these embodiments, the steps differ from those in Embodiments 1 to 3, as follows: Initially, all raw materials except the hydrogen silylation catalyst are loaded into a flask (reaction vessel), mixed, and then stripped to remove MeOH. The hydrogen silylation catalyst is then added to initiate the reaction. It should be noted that BPDG manufactured by L Company is used as the raw material, utilizing (a1-4) or (a1-2) dimethyl allyl polyether.
[0337] [Benchmark and Target Levels]
[0338] Here, Examples 4-1 and 5, which provide compositions with good viscosity, are used as references (±0%), considered practically sufficient with a viscosity reduction rate within 5% relative to these references. A viscosity reduction rate of -5% is taken as the target level. Figure 1 The solid lines in the text represent...
[0339] [Example 4-1]
[0340] In a 1L reactor, 127.12g of (a2-1)methylhydropolysiloxane, 272.88g of (a1-4) dimethyl allyl polyether (containing 500ppm of natural vitamin E), 400g of (B') BDPG (L company), and 0.16g of a MeOH(S) solution containing 5wt.% sodium acetate (N) (20wt.ppm relative to BDPG based on sodium acetate) were added. The mixture was stirred and heated under nitrogen atmosphere. MeOH was removed from the system by stripping at 75–80°C and 65–90 mmHg for 30 minutes. Pressure was restored, and 0.21mL of hydrosilylation catalyst was added. The mixture was then matured at 80–85°C for 3.5 hours, resulting in the completion of the reaction. This yielded a solution containing at least the average composition of the following ingredients in a 50:50 ratio.
[0341] [Chemical Formula 16]
[0342]
[0343] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)
[0344] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a pale yellow transparent liquid polyether-polysiloxane block copolymer composition "1862 mm2 / s, (25°C)".
[0345] Since the molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.10, it is assumed that the two ends of the copolymer are mainly polyether-terminated (i.e., the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Additionally, some Si-H groups can undergo dehydrogenation condensation with water or alcohols in the system during the reaction; therefore, it is assumed that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1 The structure consists of residues such as BDPG. It should be noted that here, the polyether moiety is a random addition of ethylene oxide and propylene oxide. This is common in Examples 4-2 to 4-3 and Comparative Example 5 below.
[0346] [Example 4-2]
[0347] 0.16 g of MeOH solution was used to replace 5 wt.% sodium acetate.
[0348] Using 0.32 g of a 5 wt.% sodium acetate MeOH solution (40 wt. ppm relative to BDPG based on sodium acetate), the experiment was performed in essentially the same manner as in Example 4-1. A pale yellow, transparent liquid polyether-polysiloxane block copolymer composition “1891 mm² / s, (25°C)” was obtained.
[0349] [Example 4-3]
[0350] 0.16 g of MeOH solution was used to replace 5 wt.% sodium acetate.
[0351] Using 0.80 g of a 5 wt.% sodium acetate MeOH solution (100 wt. ppm relative to BDPG based on sodium acetate), the experiment was performed in substantially the same manner as in Example 4-1. A pale yellow, transparent liquid polyether-polysiloxane block copolymer composition “1862 mm² / s, (25°C)” was obtained.
[0352] [Comparative Example 5: No sodium acetate used (=0wt.ppm)]
[0353] A 1L reactor was charged with 124.69g of (a2-1)methylhydropolysiloxane, 267.66g of (a1-4) dimethyl allyl polyether (containing 500ppm of natural vitamin E), and 393g of (B') BDPG (L company). The mixture was heated to 68°C under nitrogen atmosphere with stirring. 0.21mL of hydrosilylation catalyst was added, and the reaction was carried out at 70–85°C for 4 hours, after which the reaction was completed. This yielded a product containing at least the average composition of [a2-1] in a 50:50 ratio.
[0354] [Chemical Formula 17]
[0355]
[0356] (Here, a = 20, x1 = 35, y1 = 27, n < 6)
[0357] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a pale yellow transparent liquid polyether-polysiloxane block copolymer composition "624 mm² / s, (25°C)".
[0358] [Example 5]
[0359] A 3L reactor was charged with 403.92g of (a2-1) methylhydropolysiloxane, 946.08g of (a1-5) dimethyl allyl polyether (containing 500ppm of natural vitamin E), 1350g of (B') BDPG (L company), and 2.70g of a MeOH(S) solution containing 2wt.% sodium acetate (N+S) (40wt.ppm relative to BDPG based on sodium acetate). The reactor was heated while stirring under nitrogen circulation. MeOH and water were removed from the system by stripping at 55–85°C and 15–20 mmHg for 1 hour. The pressure was restored, and 0.31ml of hydrosilylation catalyst was added. The reactor was then matured at 55–85°C for 2.5 hours, resulting in the completion of the reaction. This yielded a solution containing at least the average composition of the following ingredients in a 50:50 ratio:
[0360] [Chemical Formula 18]
[0361]
[0362] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)
[0363] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a pale yellow transparent liquid polyether-polysiloxane block copolymer composition "1552 mm2 / s, (25°C)".
[0364] Since the molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.18, it is assumed that the two ends of the copolymer are mainly polyether-terminated (i.e., the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Additionally, some Si-H groups can undergo dehydrogenation condensation with water or alcohols in the system during the reaction; therefore, it is assumed that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1 The structure consists of residues such as BDPG. It should be noted that here, the polyether moiety is a random addition of ethylene oxide and propylene oxide. This is common in Comparative Example 6.
[0365] [Comparative Example 6: Sodium acetate in excess (=200wt.ppm)]
[0366] 2.70 g of MeOH solution was used to replace 2 wt.% sodium acetate.
[0367] Using 13.5 g of a 2 wt.% sodium acetate MeOH solution (200 wt. ppm relative to BDPG based on sodium acetate), the stripping time for MeOH or water was set to 3 hours, and the experiment was performed in roughly the same manner as in Example 5. A pale yellow, transparent liquid polyether-polysiloxane block copolymer composition “1193 mm² / s, (25°C)” was obtained.
[0368] [summary]
[0369] The experimental results are summarized in Table 3 below.
[0370] [Table 3]
[0371]
[0372]
[0373] *As a reference treatment in a series of experiments, a viscosity change rate of -5% was used as the "target level" when using the same dimethyl allyl polyether raw material.
[0374] In Examples 4-1 to 4-3 and Example 5, even when using BDPG manufactured by L Company with a slightly higher acid value, compositions with practically sufficient viscosity were obtained. On the other hand, in Comparative Example 5, which did not use sodium acetate as a buffer, side reactions could not be sufficiently suppressed, resulting only in a low-viscosity product. Furthermore, even in Comparative Example 6, the viscosity of the composition decreased even with an amount sufficient to neutralize the acidic substances in the BDPG manufactured by L Company. This suggests the possibility that excessive sodium acetate could actually cause side reactions, and the amount added is technically significant. Based on the above... Figure 1 The obtained polyether-polysiloxane block copolymer composition exhibits a viscosity change rate with an absolute value smaller than the aforementioned target level (a viscosity change rate of -5% relative to the reference standard) at an amount of sodium acetate addition, expressed as sodium ions, in the range of 3.8 to 43 ppm relative to BDPG. Based on this actual value, upper and lower limits for the specific sodium salt addition amount involved in this invention are determined.
[0375] These are samples from Examples 2, 3, Comparative Example 3, and Comparative Example 4-1 of this invention. 29 The summary of SiNMR analysis results shows the average structural information of the polyether-polysiloxane block copolymer (A'), which is the main component in the obtained composition. It should be noted that the average structures (mass ratios) in Table 4 are shown as molar ratios with the total number of terminal groups of component (A') set to 2.
[0376] [Table 4]: Examples 2, 3, Comparative Example 3, and Comparative Example 4-1 29SiNMR analysis results [Table 4]
[0377] <![CDATA[M R ]]> 1.97 1.97 1.97 1.96 <![CDATA[M OX ]]> 0.03 0.03 0.03 0.04 D 20.1 19.6 19.9 19.8
[0378] R=-CH2CHMeCH2O(EO) x1 (PO) y1 -, OX=OH or alkoxy group
[0379] pass 29 SiNMR could not clearly detect the difference in the average chemical structure of the main components between the examples and the comparative examples, and both appeared to be synthesized generally normally.
[0380] This is a summary of the GPC (detector: refractometer) analysis results using chloroform eluent for the samples of Example 2, Example 3, Comparative Example 3, and Comparative Example 4-1 involved in this invention. Here, the average molecular weight is a polystyrene equivalent.
[0381] [Table 5]: GPC data for each of the above samples (the copolymers are designed with a degree of polymerization n = 6).
[0382] [Table 5]
[0383]
[0384] According to the GPC analysis results, it was confirmed that all four samples yielded copolymers with a molecular weight exceeding 30,000, which is the standard for performance as a bubble stabilizer suitable for use in polyurethane microporous foams. The proportion of unreacted polyether raw materials with methyl allyl groups at both ends was also low. However, compared to the other three samples, Comparative Example 4-1 showed a slight shift in the copolymer peak towards the lower molecular weight side, and a higher residual ratio of unreacted polyether.
[0385] [Example 6]
[0386] For methylhydropolysiloxane, dimethyl allyl polyether, and (B')BDPG (L Company), the same batch as in Example 5 was used, and the input of each raw material was increased to approximately 3.5t, following the manufacturing sequence of Example 5, using 4m 3 The reactor was used for factory production trials. The factory production system could not achieve the same level of cleanliness as laboratory experiments; the hydrosilylation reaction required more time. However, at the near completion of the reaction, it became a pale yellow, transparent liquid and achieved the target viscosity. Then, it was filtered using a Zeta potentiometric adsorption filter. A pale yellow, transparent liquid polyether-polysiloxane block copolymer composition with a transmittance of T% (580 nm) = 97% and a viscosity of 1557 mm² / s (25°C) was obtained.
[0387] [Example 7: Filter material from Example 2]
[0388] 100g of the polyether-polysiloxane block copolymer composition obtained in Example 2 above was filtered through a 90mm diameter Zeta potentiometric adsorption filter, yielding 80.3g of a slightly yellow, transparent, and uniform filtrate. As a result, the transmittance T% (580nm) of the composition improved from 78% before filtration to 97% after filtration.
[0389] [Further performance evaluation of foaming agents and their significance as filters]
[0390] Example 6, prepared as an industrial-scale filter, and Example 7, prepared as a filter from Example 2 described above, were subjected to a "foam retention test" using the homogenizing mixer described later, to conduct a more detailed performance evaluation of the compositions involved in the examples, etc. Additionally, any changes in their appearance were confirmed.
[0391] [Foam Retention Capacity Test]
[0392] For the samples of Examples 2 and 7, Example 6, and Comparative Examples 4-2, the foam-retaining ability as a surfactant was tested using a homogeneous dispersion mixer according to the following steps. It should be noted that, in order to increase the stirring force, the saw blade of the disperser was fixed in the opposite direction to the rotation direction.
[0393] [step]
[0394] 1. Place 30g of foaming agent sample into a clean 200mL wide-mouth glass bottle and let it stand.
[0395] 2. Measure and record the liquid level of the sample. Draw a line along the meniscus with an oil-based magic pen, and treat the height of the upper end of the line as the initial height of the liquid level. Generally, the lower end of the line should be 18 mm from the bottom of the bottle, and the upper end of the stopper should be 20 mm from the bottom of the bottle.
[0396] 3. Immerse the saw blade of the homogenizer into the center of the liquid, setting the height slightly above the level so that the saw blade does not touch the bottom of the glass bottle.
[0397] 4. Secure the glass bottle containing the sample with clamps.
[0398] 5. Use a homogenizer to stir at 3000 rpm for 2 minutes.
[0399] 6. After stirring stops, move the saw blade to a height of about 1 cm without contacting the foaming liquid and fix it in place. Run it idle for a short time to remove the liquid adhering to the saw blade.
[0400] 7. Remove the glass bottle and mark the height (top) of the foam with an oil-based magic pen. Calculate the difference between this height and the initial height [cm]. The magnitude of this value determines the foam's holding power.
[0401] Note) Steps 6 and 7 are performed within a short period of approximately 30 seconds. Observations after the experiment show that...
[0402] The height of the generated foam remains almost unchanged for at least 3 to 5 minutes.
[0403] For the above samples, the long-term storage stability at room temperature was evaluated by measuring appearance and transmittance.
[0404] In addition, for the above samples, Na [ppm] was quantified by acid decomposition-ICPMS method. The analytical value was obtained as the average of the two measurements.
[0405] Table 6 below summarizes the test results for foam retention capacity, storage stability, and Na content. [Table 6]: Relationship between foam retention capacity, storage stability, and Na content of the samples
[0406] [Table 6]
[0407]
[0408] *Analytical values obtained through ICPMS quantitative methods
[0409] Table 6 revealed an unexpected benefit: the composition containing "polyether-polysiloxane block copolymer (A')" obtained by the manufacturing method of the present invention does not exhibit adverse effects such as separation even without filtration, and maintains the properties of a homogeneous liquid (Example 2). However, filtration further improves the stability of the appearance and enhances the foam retention (Example 7). Comparative Examples 4-2, which do not contain sodium salt, have high viscosity and should generally possess properties advantageous as a foam stabilizer, but the same effect could not be confirmed. On the other hand, Example 7, where the sodium ion content is reduced through filtration, also exhibits superior foam retention compared to Example 2, which contains the same polymer components. Therefore, the relationship between the sodium content [ppm] in the composition and the foam retention [cm] of the polyether-polysiloxane block copolymer composition was plotted on... Figure 2 middle.
[0410] exist Figure 2In this study, the target value for foam retention was set at 4.0 cm. Based on this graph, preliminary calculations determined that the sodium content required to achieve the target level of foam retention in the polyether-polysiloxane block copolymer composition was approximately 0.6–6.7 wt.ppm relative to the composition (specifically, the sum of component (A”) and component (B)). This range is critical; unlike the sodium content in the manufacturing process, by controlling the sodium content in the final composition within the aforementioned range, a new function—foam reinforcement—that is entirely different from its effect as a buffer was confirmed.
[0411] Further, the samples from Example 7 and Comparative Examples 4-2 were mixed with polypropylene glycol (average molecular weight 425, abbreviated as PPG-425), a type of polyether polyol, to prepare a premixed solution. At this time, since the mass ratio of sample to PPG was 6.0 g: 24.0 g, the concentration of the polyether-polysiloxane block copolymer (A') in the solution was 10 wt.%. These were subsequently designated as Example 8 and Comparative Example 7.
[0412] According to the [Foam Retention Test] and [Procedure] described above, the foam retention properties of these premixed solutions were tested. PPG-425 (30g) without a foam stabilizer was used as a reference sample in this test. The results are summarized in Table 7 below. The foam volume increase rate [%] in the table is calculated based on the data of Comparative Example 7 using the sample from Comparative Example 4-2 (set to zero).
[0413] [Table 7]: Foam retention power of premixed solutions
[0414] [Table 7]
[0415]
[0416] Comparative Example 7 used the foaming agent composition of Comparative Example 4-2, which has extremely high viscosity and is generally considered to possess advantageous properties as a foaming agent, and its practically effective performance was confirmed in this test. However, the premixed solution of Example 8, which used the foaming agent of Example 7 with a much lower viscosity, exhibited superior foaming or foam retention properties compared to Comparative Example 7, achieving a large foam-enhancing effect above the polymer viscosity or molecular weight in a polyether-polysiloxane block copolymer composition containing a very limited amount of sodium monovalent carboxylate.
[0417] [Examples 9-11: Compositions containing component (C) and their compatibility evaluation]
[0418] In the following experiments, the compatibility of the sample of Example 6 (hereinafter referred to as "Sample Ex" or "Ex") with various polyether polyols or polydiol derivatives was investigated. Substances exhibiting excellent compatibility with Sample Ex can be used as diluents for the "composition comprising a polyether-polysiloxane block copolymer (A')" obtained by the manufacturing method of the present invention, and can constitute the foam stabilizer for polyurethane foams according to the present invention. Alternatively, they can be considered suitable as base polyols for formulating premixes for polyurethane foams according to the present invention. As another effect of these diluents, the hydroxyl value of the foam stabilizer can be adjusted, thereby enabling control over the effect on the pre-designed strength or crosslinking density of the polyurethane foam. Furthermore, it is also effective for controlling the air permeability or cell size of the foam.
[0419] Here, the positioning of Examples 9 to 11 is as follows.
[0420] Example 9: Compatibility evaluation test of Ex sample and polyether alcohol (C1)
[0421] Example 10: Compatibility evaluation test of Ex sample and polyether diol (C2)
[0422] Example 11: Compatibility evaluation test of Ex sample and polyether triol (C3)
[0423] [Compatibility Evaluation Test]
[0424] The Ex sample and component (C) were mixed in three stages at a total of 10g, with the Ex / C ratios being 5.0g / 5.0g, 2.0g / 8.0g, and 0.5g / 9.5g. The compatibility test was then performed according to the following steps: visual confirmation of the liquid appearance.
[0425] [step]
[0426] 1. Plug the spiral tube, shake it up and down to mix thoroughly about 10 times, and then let it stand in a constant temperature bath at 50℃ for about 10 to 15 minutes to largely eliminate air bubbles.
[0427] 2. After recording the appearance at 50°C, remove the spiral tube and allow it to return to room temperature.
[0428] 3. After recording the appearance at room temperature, for samples with uneven, cloudy appearance, let them stand overnight for further observation. For samples that are translucent to transparent and appear uniform, let them stand in a refrigerator at 5°C for 1 to 2 hours and observe the changes in appearance.
[0429] 4. After recording the appearance of the sample placed in the refrigerator at 5°C, remove the spiral tube and allow it to return to room temperature. Additionally, confirm that the appearance at room temperature is not significantly different from the appearance recorded in step 3 (room temperature).
[0430] 5. Record the appearance of the sample that turned cloudy in step 3 after standing overnight.
[0431] It should be noted that the evaluation of appearance is recorded according to the following criteria.
[0432] * Set the intermediate case between the two to "~".
[0433] ◎: Transparent and homogeneous liquid
[0434] 〇: Semi-transparent to mostly transparent homogeneous liquid
[0435] Δ: Translucent homogeneous liquid
[0436] ×: Opaque, cloudy white liquid
[0437] <Example 9: Compatibility Evaluation Test with Polyether Alcohol (C1)>
[0438] The results of evaluating the compatibility of the Ex sample with polyether alcohols (C1) having the structures and molecular weights shown in Table 8 are presented in Table 8.
[0439] [Table 8]
[0440]
[0441] Note) Regarding the structure of C1 in Table 8, for simplicity, the EO chain and PO chain are denoted as block copolymers, but in reality they are random copolymers.
[0442] <Example 10: Compatibility Evaluation Test with Polyether Diol (C2)>
[0443] The results of the compatibility evaluation of the Ex sample and polyether diols (C2) with the structures and molecular weights shown in Table 9 are presented in Table 9.
[0444] [Table 9]
[0445]
[0446] Note) Regarding the structure of C2 in Table 9 (Comparative Example 9-1), for simplicity, the EO chain and PO chain are denoted as block copolymers, but in reality they are random copolymers.
[0447] <Example 11: Compatibility Evaluation Test with Polyether Triol (C3)>
[0448] The results of the compatibility evaluation of the Ex sample and polyether triols (C3) with the structures and molecular weights shown in Table 10 are presented in Table 10.
[0449] [Table 10]
[0450]
[0451]
[0452] Note) The structure of C3 in Table 10 (Comparative Example 10-1) is an EO / PO random copolymer.
[0453] [About ingredient (C1)]
[0454] As shown in Table 8, when polyether alcohol is used as a diluent, in the case of homopolymer addition polymer of PO (propylene oxide), even when the molar addition number approaches 40 and becomes a long chain, the compatibility with component (A') is maintained, and the stability of the mixture is good. On the other hand, in the case of addition copolymer of EO (ethylene oxide) and PO, with EO wt.% = 50 and set to a constant value, and molecular weights set to 500, 1000, and 3000, the results show that the stability deteriorates drastically when the total molar addition number of EO exceeds 30. Furthermore, the homopolymer addition polymer of EO is completely immiscible with component (A'), thus clarifying the need for PO polymerization units in the structure of polyether alcohol.
[0455] Based on these results, when polyether alcohol is used as a diluent, the upper limit of the molar addition of EO is estimated to be around 20, the upper limit of the molar addition of PO is estimated to be around 50, and the upper limit of EO wt.% in the structure is estimated to be around 60. According to the experience of the inventors, when the wt.% of EO in the polyether alcohol is 70 or higher, the freezing point rises, and it tends to produce precipitates or a cloudy appearance at low winter temperatures. Therefore, in this invention, the upper limit of EO wt.% when polyether alcohol is used as a diluent is set to around 60.
[0456] [About ingredient (C2)]
[0457] As shown in Table 9, when polyether glycol is used as a diluent, even when the homopolymer of PO (propylene oxide) is a long chain with an addition molar number of around 35, the compatibility with component (A') is very good, and the stability of the mixture is also good. When the addition molar number of PO is around 70, a decrease in compatibility is confirmed, but it is considered that the stability of the mixture is within acceptable limits under conditions of high concentration of component (A') such as Ex / C2 = 50 / 50, and it is believed that it can also be used as a foaming agent. On the other hand, as an addition copolymer of EO (ethylene oxide) and PO, an addition copolymer with EO wt.% = 50 and a molecular weight of 1750 was tested, but it was found that the stability deteriorated drastically.
[0458] Based on these results, when polyether glycol is used as a diluent, the upper limit of the molar addition of EO is estimated to be around 10, the upper limit of the molar addition of PO is estimated to be around 70, and the upper limit of wt.% of EO in the structure is estimated to be around 30.
[0459] [About ingredient (C3)]
[0460] As shown in Table 10, it was confirmed that the compatibility of polyether triol with the compositions of the present invention, which are mainly composed of components (A') and (B'), tends to be slightly reduced compared to polyether diol or polyether monool. In the case of polyether triol as a homopolymer addition polymer of PO, insufficient compatibility was observed at a mixing ratio of Ex / C3 = 20 / 80. However, under conditions of high concentration of component (A') such as Ex / C3 = 50 / 50, the stability of the mixture was within acceptable limits, and it was considered that it could be used as a foam stabilizer. Furthermore, even under conditions of low concentration of component (A') such as Ex / C3 = 5 / 95 (assuming the case of a premix for polyurethane foam), the stability of the mixture was within acceptable limits. On the other hand, as an addition copolymer of EO (ethylene oxide) and PO, an addition copolymer with EO wt.% = 50 and a molecular weight of 2800 was tested, but it was found that the stability was extremely deteriorated.
[0461] Based on these results, when polyether triol is used as a diluent, the upper limit of EO wt.% in its structure is estimated to be around 20, and the average molecular weight range is estimated to be about 500 to 4500.
[0462] [Summarize]
[0463] Through the above embodiments, etc., by using the manufacturing method including the improved hydrosilylation reaction process of steps 1 to 3 involved in the present invention, it is possible to significantly improve the production efficiency of compositions containing polyether-polysiloxane block copolymers (A') and foam stabilizers using inexpensive and high-acid-value glycol ether compounds (B') as raw materials, and to solve their quality problems. Even when using raw materials such as dimethyl allyl polyether with quality deviations, good reproducibility of its technical effects can be confirmed.
[0464] In particular, the present invention provides a preferred buffering agent composition or buffering system that can achieve the same quality as when using a cheap glycol ether compound (B') with a very low acid value and a high price, even when using an inexpensive glycol ether compound (B') as a raw material, and a preferred manufacturing method for the (AB)n type polyether modified silicone composition of the buffering agent by specifying the range of preferred addition amounts of the buffering agent.
[0465] Furthermore, according to the present invention, it has been confirmed that in compositions comprising polyether-polysiloxane block copolymers (A”) with a specific structure, when the content of glycol ether compound (B’) and sodium salt is within a very limited range, compositions exhibiting foam-enhancing properties different from those conventionally achieved by sodium salts as buffers are possible. Similarly, practically sufficient insights have been gained regarding the preferred combinations and compatibility relationships of the compositions and components (C) involved in the present invention.
[0466] Based on the above experimental results, it is understood and expected that the present invention will solve the previous quality and process problems through simple means, and will enable the low-cost, stable and large-scale supply of the polyether-polysiloxane block copolymer composition, the improved manufacturing method thereof, the composition with excellent cost utilization and foam reinforcement, and the foaming agent for polyurethane foam composed therefrom.
Claims
1. A method for manufacturing a composition, the method comprising: step 1: Will include at least (a1) From the following general formula (1) General formula (1): The term refers to polyethers with alkenyl groups at both ends; and (N+S) is a sodium salt solution containing the following components (N) and (S): (N) Sodium monovalent carboxylate salts with 2 to 18 carbon atoms (S) is a solvent selected from (S1) water and (S2) a monohydric saturated alcohol having 1 to 4 carbon atoms. The process of mixing raw material components; In equation (1), x is a number from 2 to 4, and y represents the result of (C x H 2x O)y represents the molecular weight of the polyether moiety in the range of 400 to 5000, Y represents a monovalent hydrocarbon group with 2 to 8 carbon atoms at the end having a reactive C=C group, and the polyether moiety contains at least one propylene oxide group; Process 2: The process of removing the solvent (S) from step 1 to the outside of the system by heating and / or reducing pressure; Process 3: After step 2, the component (a1) and (a2) From the following general formula (2): General formula (2): This refers to organopolysiloxanes containing SiH groups at both ends. In the component (N), (B') One or more glycol ether compounds, characterized in that, The terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and secondary alcoholic hydroxyl groups at other ends; the repeating number of the 2 to 4 carbon oxidized alkene units is in the range of 1 to 3; and it does not contain heteroatoms other than oxygen; and The process of carrying out the hydrosilylation reaction is performed in the presence of an effective amount of hydrosilylation reaction catalyst; In formula (2), R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have aliphatic unsaturated bonds, and a represents a number from 1 to 200; When the total amount of components (a1), (a2), and (B') is set to 100 parts by weight, the amount of component (B') used is in the range of 40 to 80 parts by weight, and relative to the amount of component (B') used, the sodium cation (Na) in component (N) + The content of ) ranged from 3.8 to 43 ppm by weight. The composition comprises an intramolecular element having the following general formula (3): General formula (3): The structural unit represented is a polyether-polysiloxane block copolymer (A'); In equation (3), R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have an aliphatic unsaturated bond, a represents a number from 1 to 200, x is a number from 2 to 4, and y represents a group composed of (C x H 2x O)y represents a polyether moiety with a molecular weight in the range of 400 to 5000, n is a number with at least 2, and Y' represents a divalent hydrocarbon group with 2 to 8 carbon atoms bonded to adjacent silicon atoms via carbon-silicon bonds and to polyoxyethylene blocks via oxygen atoms.
2. The method for manufacturing the composition according to claim 1, characterized in that, The above steps 1 to 3 are carried out in a reaction vessel.
3. The method for manufacturing the composition according to claim 1 or 2, wherein, The above-mentioned step 1 is a process of mixing the component (a1), the component (N+S), and one or more other raw material components selected by arbitrary selection, and is a mixing process of raw material components. In step 1, the component (a2) in the raw material components does not coexist with the hydrogen silylation reaction catalyst in the raw material system.
4. The method for manufacturing the composition according to claim 1, wherein, Component (A') has a component selected from [a specific ingredient] at the end of its molecular chain. Z 1 : Alkenyl, hydroxyl, alkoxy, or acetoxy groups that are partially bonded to the polyether; and Z 2 Monovalent hydrocarbon groups, hydroxyl groups, alkoxy groups, or C1-C8 alkylene oxide groups bonded to silicon atoms and without heteroatoms A polyether-polysiloxane block copolymer with one or more functional groups.
5. The method for manufacturing the composition according to claim 1, the method further comprising a step of filtering the composition obtained in step 3 such that the transmittance at 580 nm is 90% or more.
6. The method for manufacturing the composition according to claim 1, wherein, In the general formulas (2) and (3), a is a number in the range of 10 to 45. In the general formulas (1) and (3), y is the expression that makes (C x H 2x The molecular weight of the polyether portion represented by O)y is in the range of 1500 to 5000, and the average content of the ethylene oxide unit C2H4O relative to the total content of the polyether portion is in the range of 30% to 80% by mass.
7. The method for manufacturing the composition according to claim 1, wherein, Component (B') is one or more glycol ethers selected from propylene glycol monobutyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monobutyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, propylene glycol monopropyl ether, dipropylene glycol monopropyl ether, tripropylene glycol monopropyl ether, propylene glycol monoethyl ether, dipropylene glycol monoethyl ether, and tripropylene glycol monoethyl ether.
8. The method of manufacturing the composition according to claim 1, wherein the method of manufacturing the composition further includes, after step 3, A step of adding (C) a polyether compound that is compatible with the composition comprising (A') and (B') and selected from (C1) to (C3) below, and then mixing and homogenizing the mixture, wherein... The amount of component (C) used is such that the content of component (A') in the final composition is 1% by weight or more, wherein, (C1) Polyether alcohol represented by the following general formula (4) General formula (4): In formula (4), R represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have aliphatic unsaturated bonds, R'' represents methyl or ethyl, k satisfies the condition 0≤k≤20, l satisfies the condition 4≤l≤50, and the weight % of the oxyethylene part of the polyether portion is less than 60%. (C2) Polyether diols represented by the following general formula (5) General formula (5): In formula (5), R'' represents methyl or ethyl, k' satisfies the condition 0≤k'≤10, l' satisfies the condition 4≤l'≤70, and the weight % of the ethylene oxide portion of the polyether portion is less than 30%. (C3) The polyether triol is obtained by addition polymerization of 2-4 carbon alkyl esters to glycerol and / or trimethylolpropane, with the ethylene oxide portion of the polyether fraction being less than 20% by weight and the average molecular weight being in the range of 500 to 4500.
9. The method of manufacturing the composition according to claim 1, further comprising the step of adding an antioxidant at any time, in the range of 1 to 1000% by weight, relative to 100 parts by weight of the sum of the components (A') and (B').
10. A composition comprising (A'') having, within the molecule, the formula (3'): General formula (3'): The structural unit represented is a polyether-polysiloxane block copolymer; In equation (3'), R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have an aliphatic unsaturated bond, a is a number in the range of 10 to 45, x is a number in the range of 2 to 4, and y represents the group formed by (C x H 2x O) y The molecular weight of the polyether portion is in the range of 1500 to 5000, and the average content of the ethylene oxide unit relative to the total polyether portion is 30 to 80% by mass. The polyether portion contains at least one propylene oxide group, n is at least 2, and Y' represents a divalent hydrocarbon group with 2 to 8 carbon atoms bonded to adjacent silicon atoms by carbon-silicon bonds and bonded to polyoxyethylene blocks by oxygen atoms. (B') One or more glycol ether compounds, characterized in that, The terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and secondary alcoholic hydroxyl groups at other ends; the repeating number of the 2 to 4 carbon oxidized alkene units is in the range of 1 to 3; and it does not contain heteroatoms other than oxygen; and (N) Sodium monovalent carboxylate salts with 2 to 18 carbon atoms. The mass ratio of component (A'') to component (B') is in the range of 20:80 to 60:40, and the component (N) contains sodium cations (Na) in the range of 0.6 to 6.7 ppm by weight relative to the sum of components (A'') and (B'). + A composition of ).
11. The composition according to claim 10, further comprising (C) a polyether compound that is compatible with the composition comprising component (A'') and component (B') and selected from components (C1) to (C3) below: (C1) Polyether alcohol represented by the following general formula (4) General formula (4): In formula (4), R represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have aliphatic unsaturated bonds, R'' represents methyl or ethyl, k satisfies the condition 0≤k≤20, l satisfies the condition 4≤l≤50, and the weight % of the oxyethylene part of the polyether portion is less than 60%. (C2) Polyether diols represented by the following general formula (5) General formula (5): In formula (5), R'' represents methyl or ethyl, k' satisfies the condition 0≤k'≤10, l' satisfies the condition 4≤l'≤70, and the weight % of the ethylene oxide portion of the polyether portion is less than 30%. (C3) The polyether triol is obtained by addition polymerization of 2-4 carbon alkyl esters to glycerol and / or trimethylolpropane, with the ethylene oxide portion of the polyether fraction being less than 20% by weight and the average molecular weight being in the range of 500 to 4500.
12. The use of a composition obtained by the method of manufacturing the composition according to any one of claims 1 to 9, or the composition according to any one of claims 10 to 11, as a surfactant, a foam stabilizer for polyurethane foam, or a premix for polyurethane foam.
13. A method for manufacturing a surfactant, a foam stabilizer for polyurethane foam, or a premix for polyurethane foam, comprising a method for manufacturing the composition according to any one of claims 1 to 9.
14. A polyurethane foam forming composition comprising a composition obtained by the method of manufacturing the composition according to any one of claims 1 to 9, or a composition according to any one of claims 10 to 11.
15. A polyurethane foam, said polyurethane foam being made from a composition obtained by the method of manufacturing the composition according to any one of claims 1 to 9, or the composition according to any one of claims 10 to 11.
Citation Information
Patent Citations
JP1973075314A
katoseihoriesuteruretanfuoomu
JP1976001598A
Monitoring system for transmission circuit
JP1979022115A
Surfactant
JP1981022395A
Surfactant
JP1982014797B2
